Adhesive composition for coated polarizing element, adhesive sheet for coated polarizing element, adhesive sheet for image display device constituent member, adhesive sheet with release film, adhesive sheet with image display device constituent member, laminated sheet, coated polarizing element with adhesive layer, adhesive sheet with polarizing element, image display device
Patent Information
- Application Number
- CN202180076983.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-27
- Filing Date
- 2021-10-12
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-10-12
AI Technical Summary
[0004]然而,这种现有的偏光板使用拉伸了聚乙烯醇(PVA)薄膜的偏振片,因此,非常脆,需要由2张保护薄膜夹持,因而在薄膜化上存在限度
[0028]本发明的涂布型偏振元件用粘合剂组合物或涂布型偏振元件用粘合片通过与涂布型偏振元件组合使用从而可以防止该涂布型偏振元件由于外部光等光而导致的偏振性能经时降低的情况。由此,可以将涂布型偏振元件与其他图像显示装置构成构件进行贴合一体化而不如现有那样使用保护薄膜,而且还可以防止光劣化,因此,可以有利于图像显示装置的薄膜化、轻量化和耐光劣化性的改善。
Smart Images

Figure GDA0004324513420000421 
Figure GDA0004324513420000431 
Figure GDA0004324513420000441
Abstract
Description
Technical Field
[0001] This invention relates to adhesive compositions suitable for use in organic electroluminescence (hereinafter also referred to as "organic EL"). In particular, it relates to: adhesive compositions suitable for use in coated polarizing elements; adhesive sheets for coated polarizing elements formed from the adhesive compositions; adhesive sheets with polarizing elements having coated polarizing elements; image display devices using the adhesive sheets; coated polarizing elements having adhesive layers formed from the aforementioned adhesive compositions; and image display devices using coated polarizing elements with adhesive layers. Additionally, it relates to: adhesive sheets for bonding components of image display devices suitable for use in attaching components of image display devices; adhesive sheets with release films using the aforementioned adhesive sheets for image display device components; adhesive sheets with image display device components; laminated sheets; and image display devices. Background Technology
[0002] In recent years, with the trend of thin-film and lightweight image display devices such as liquid crystal display devices and organic EL display devices, thin-film technology is also required for optical anisotropic components such as polarizing plates and phase retardation plates that constitute image display devices.
[0003] Existing polarizing plates are typically constructed by coating an adhesive or laminating adhesive sheets onto a structure consisting of a protective film such as a TAC (cellulose triacetate) film sandwiching a polyvinyl alcohol (PVA) film. Examples of known polarizing plates include those constructed by laminating adhesive layers / protective films / polarizing films / protective films / adhesive layers, or adhesive layers / protective films / polarizing films / phase retardation plates / adhesive layers, etc.
[0004] However, this existing polarizer uses a polarizer with a stretched polyvinyl alcohol (PVA) film, which is very brittle and requires two protective films to hold it in place, thus limiting its thin-film application.
[0005] Therefore, coated polarizing elements, such as polarizing plates, have attracted much attention as a means of making polarizing elements thinner.
[0006] Liquid crystal compounds with polymerizable functional groups (also known as "polymerizable liquid crystal compounds") possess both the properties of polymerizable monomers and liquid crystals. Therefore, when polymerized and cured in an oriented state, a cured product formed from a polymer with fixed orientation can be obtained, i.e., an optically anisotropic material.
[0007] Therefore, by coating an optically anisotropic composition containing a polymeric liquid crystal compound onto a substrate and curing it in an oriented state, a polarizing film with optical anisotropy can be formed. The polarizing element thus obtained is generally referred to as a coated polarizing element.
[0008] On the other hand, in order to suppress light degradation of the components of an image display device, an adhesive sheet containing an ultraviolet absorber is known to be disposed between a surface protection panel and an image display component.
[0009] For example, Patent Document 1 discloses an adhesive sheet having an acrylic adhesive layer, a b* value of 0.42 or less, and a light transmittance of 5% or less for a wavelength of 350 nm.
[0010] In addition, Patent Document 2 discloses an ultraviolet-curable acrylic adhesive layer disposed between a glass cover or plastic cover and a polarizing film in an image display device, wherein the transmittance at a wavelength of 380 nm is less than 40% and the transmittance at a wavelength of 400 nm is more than 30%.
[0011] Existing technical documents
[0012] Patent documents
[0013] Patent Document 1: Japanese Patent Application Publication No. 2019-214722
[0014] Patent Document 2: Japanese Patent Application Publication No. 2016-155981 Summary of the Invention
[0015] The problem the invention aims to solve
[0016] Compared with existing polarization elements, the aforementioned coated polarization element can form a film through coating, thus reducing its thickness.
[0017] However, this type of coated polarization element is easily degraded by light, and therefore, there is a problem that the polarization performance will decrease over time due to external light and other light.
[0018] In addition, not only polarizing elements, but also various optical components such as iodine used in polarizing plates, dichroic organic pigments, liquid crystal panels used in image display devices, and organic EL elements suffer from insufficient light resistance.
[0019] Therefore, it is considered appropriate to use the aforementioned adhesive sheet containing ultraviolet absorber in coated polarizing elements.
[0020] However, for the transparent adhesive for image display devices with light absorption function in the aforementioned patent documents 1 and 2, since it is not considered to use it in combination with a coated polarizing element, it is difficult to prevent the polarization performance of the coated polarizing element from decreasing over time due to external light or other light when used with a coated polarizing element.
[0021] Therefore, the objective of this invention is to provide an adhesive composition or adhesive sheet for a coated polarizing element that, when used in combination with a coated polarizing element, can prevent the polarization performance of the coated polarizing element from degrading over time due to exposure.
[0022] Furthermore, the image display devices with light absorption functions in the aforementioned patent documents 1 and 2 supplement the function of the protective film layer that protects the polarizing plate from ultraviolet rays, i.e., the protective film layer containing ultraviolet absorbers, using a transparent adhesive. Therefore, in order to cope with the further thinning and lightweighting of image display devices, it is required to suppress the light degradation of optical components without setting a protective film layer. For this reason, the adhesive itself needs to have light resistance reliability.
[0023] Therefore, another objective of the present invention is to provide an adhesive sheet for image display device components that exhibits excellent lightfastness and reliability, enabling the thin-film and lightweight construction of image display devices.
[0024] Solution for solving the problem
[0025] To address the aforementioned issues, the present invention provides an adhesive composition for coating polarizing elements and an adhesive sheet for coating polarizing elements comprising an adhesive layer formed using the composition. The adhesive composition for coating polarizing elements is an adhesive composition comprising a (meth)acrylic polymer (A), an ultraviolet absorber (B), and a free radical polymerization initiator (C). The transmittance of the adhesive layer formed from the aforementioned adhesive composition at a wavelength of 400 nm is 50% or less.
[0026] The present invention also proposes an adhesive sheet for a component of an image display device, which is formed of an adhesive composition comprising a (meth)acrylic acid copolymer (A), a hydroxyl-containing benzophenone compound (B1) and a free radical polymerization initiator (C), and has a transmittance of less than 30% at a wavelength of 400 nm.
[0027] The effects of the invention
[0028] The adhesive composition or adhesive sheet for coated polarizing elements of the present invention, when used in combination with a coated polarizing element, can prevent the polarization performance of the coated polarizing element from degrading over time due to external light or other light. Therefore, the coated polarizing element can be integrated with other components of the image display device without the need for a protective film as in the past, and light degradation can also be prevented. Thus, it is beneficial for improving the thin-film design, weight reduction, and light degradation resistance of the image display device.
[0029] The adhesive sheet for the components of the image display device proposed in this invention has excellent light resistance reliability. Therefore, the components of the image display device can be bonded together as an integral unit without the need for a protective film layer to protect the polarizing plate from ultraviolet rays, i.e., a protective film layer containing ultraviolet absorbers, as is the case with existing methods. Moreover, it can prevent light degradation of the components of the image display device. Therefore, it can help improve the thin-film design, weight reduction and light resistance of the image display device. Attached Figure Description
[0030] Figure 1 This is a cross-sectional view illustrating an example of an adhesive sheet with a polarizing element or an adhesive sheet constituting an image display device according to the present invention.
[0031] Figure 2 This is a cross-sectional view illustrating an example of the image display device of the present invention.
[0032] Figure 3 This is a cross-sectional view illustrating an example of the image display device of the present invention.
[0033] Figure 4 This is a cross-sectional view illustrating an example of the image display device of the present invention.
[0034] Figure 5 This is a cross-sectional view illustrating an example of the image display device of the present invention.
[0035] Figure 6 A cross-sectional view illustrating an example of the adhesive sheet with a release film according to the present invention.
[0036] Figure 7 This is a cross-sectional view illustrating an example of the laminated sheet of the present invention. Detailed Implementation
[0037] Next, the present invention will be described based on exemplary embodiments. However, the present invention is not limited to the embodiments described below.
[0038] <<This adhesive composition I>>
[0039] An example of an embodiment of the present invention is an adhesive composition I for a coating-type polarizing element (referred to as "this adhesive composition I") comprising a (meth)acrylic polymer (A), an ultraviolet absorber (B), and a free radical polymerization initiator (C), and optionally includes a multifunctional (meth)acrylic ester (D) and other components.
[0040] It should be noted that in this invention, "(meth)acrylic polymers" means that there are acrylic copolymers and methacrylic copolymers, "(meth)acrylates" means that there are acrylates and methacrylates, and "(meth)acryloyl" means that there are acryloyl groups and methacryloyl groups.
[0041] Furthermore, in this invention, "polarizing element" refers to an optical component possessing optical anisotropy, and "coated polarizing element" refers to a laminate comprising a film formed by coating an optically anisotropic composition containing a liquid crystal compound. Examples of the aforementioned liquid crystal compound include polymeric liquid crystal compounds, high molecular weight liquid crystal compounds, and lyotropic liquid crystal compounds. For example, a cured product formed by coating an optically anisotropic composition containing a polymeric liquid crystal compound onto a substrate and curing it in an oriented state can be used as a polarizing element. In this case, the substrate may or may not be included.
[0042] This adhesive composition I, as described below, can be cured by heat or by active energy rays. In particular, curing by active energy rays eliminates the need for curing and is preferred for its superior productivity.
[0043] This adhesive composition I, as described below, can be cured in multiple stages.
[0044] Furthermore, when curing by active energy rays, in the case of adhesive sheets containing ultraviolet absorbers, the ultraviolet absorbers hinder curing under active energy rays. Therefore, it is usually difficult to use active energy ray curing systems. However, this invention dares to apply it, and as a result, a good adhesive sheet can be obtained.
[0045] <(Meth)acrylic polymers (A)>
[0046] As for the aforementioned (meth)acrylic polymer (A), in addition to homopolymers of alkyl (meth)acrylic esters, copolymers obtained by polymerization with monomer components that can copolymerize with them can also be cited.
[0047] Examples of such copolymers include copolymers formed by copolymerizing alkyl (meth)acrylates (a1) whose main alkyl group has 4 to 18 carbon atoms with monomers that can copolymerize with them.
[0048] It should be noted that the aforementioned main component refers to the component that has a significant impact on the properties of the (meth)acrylic polymer (A). The content of this component is usually 30% or more by mass of the total (meth)acrylic polymer (A), preferably 35% or more by mass, more preferably 50% or more by mass, and particularly preferably 60% or more by mass.
[0049] The aforementioned (meth)acrylic polymer (A) may contain two or more different (meth)acrylic polymers.
[0050] Examples of the aforementioned "alkyl (meth)acrylates (a1) having 4 to 18 carbon atoms" include, for example, n-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, etc., as well as linear alkyl (meth)acrylates, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, etc. Tert-butyl acrylate, isoamyl acrylate, neopentyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, isononyl acrylate, isodecanyl acrylate, isostearyl acrylate, isostearyl acrylate, branched alkyl acrylates, cyclohexyl acrylate, tert-butylcyclohexyl acrylate, 3,5,5-trimethylcyclohexane acrylate, dicyclopentyl acrylate, dicyclopentenyl acrylate, dicyclopentenoxyethyl acrylate, isobornyl acrylate, etc., alicyclic acrylates, etc. These can be used alone or in combination of two or more.
[0051] From the viewpoint of improving stress relief and heat resistance reliability when forming adhesive sheets or adhesive layers, the content of the above-mentioned alkyl methacrylate (a1) is preferably 30% by mass or more, more preferably 40% by mass or more, further preferably 50% by mass or more, particularly preferably 60% by mass or more, and most preferably 65% by mass or more, relative to the overall composition of the (meth)acrylate polymer (A).
[0052] Furthermore, regarding the content of the aforementioned alkyl methacrylate (a1), from the viewpoint of suppressing the reduction of adhesive strength, it is preferably 90% by mass or less, more preferably 85% by mass or less, further preferably 80% by mass or less, particularly preferably 75% by mass or less, and most preferably 70% by mass or less, relative to the overall composition of the (meth)acrylate polymer (A).
[0053] Examples of monomer components that can copolymerize with alkyl (meth)acrylates (a1) having 4 to 18 carbon atoms of the aforementioned alkyl group include hydroxyl-containing monomers (a2), alkyl (meth)acrylate monomers or vinyl ester monomers having 1 to 3 carbon atoms of the alkyl group (a3), olefinic unsaturated monomers containing functional groups (a4) (excluding hydroxyl-containing monomers (a2)), and other copolymerizable monomers (a5).
[0054] Examples of the aforementioned "hydroxyl-containing monomers (a2)" include, for instance, hydroxy esters of methacrylates such as 2-hydroxyethyl methacrylate, 4-hydroxybutyl methacrylate, 5-hydroxypentyl methacrylate, 6-hydroxyhexyl methacrylate, and 8-hydroxyoctyl methacrylate; caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl methacrylate; alkylene oxide-modified monomers such as diethylene glycol methacrylate and polyethylene glycol methacrylate; primary hydroxyl-containing monomers such as 2-acryloyloxyethyl-2-hydroxyethyl phthalate; secondary hydroxyl-containing monomers such as 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, and 3-chloro-2-hydroxypropyl methacrylate; and tertiary hydroxyl-containing monomers such as 2,2-dimethyl-2-hydroxyethyl methacrylate. These can be used alone or in combination of two or more.
[0055] Among the hydroxyl-containing monomers (a2) mentioned above, monomers containing primary hydroxyl groups are preferred in terms of excellent balance between resistance to damp heat and heat resistance, particularly 2-hydroxyethyl methacrylate, 4-hydroxybutyl methacrylate, and 2-hydroxypropyl methacrylate, and especially 2-hydroxyethyl methacrylate and 4-hydroxybutyl methacrylate.
[0056] From the viewpoint of improving resistance to damp heat, the lower limit of the content of the hydroxyl-containing monomer (a2) is generally 3% by mass or more, preferably 5% by mass or more, more preferably 8% by mass or more, further preferably 10% by mass or more, and particularly preferably 12% by mass or more, relative to the overall composition of the (meth)acrylic polymer (A).
[0057] On the other hand, from the viewpoint of inhibiting the self-crosslinking reaction of the adhesive composition, improving processability and heat resistance reliability, the upper limit of the content of the hydroxyl-containing monomer (a2) is generally 60% by mass or less, preferably 45% by mass or less, more preferably 35% by mass or less, further preferably 30% by mass or less, and particularly preferably 25% by mass or less.
[0058] Examples of the aforementioned "(meth)acrylate monomers or vinyl ester monomers (a3) having 1 to 3 carbon atoms in the alkyl group" include, for example, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, vinyl propionate, and vinyl acetate. These monomers (a3) can be used alone or in combination of two or more.
[0059] From the viewpoint of improving cohesiveness when used as an adhesive, methyl methacrylate and ethyl methacrylate are preferred among the components described above (a3).
[0060] Furthermore, regarding the lower limit of the content of the aforementioned component (a3), from the viewpoint of improving the cohesive strength when used as an adhesive, it is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 10% by mass or more, relative to the overall composition of the (meth)acrylic polymer (A). Furthermore, regarding the upper limit of the content of the aforementioned component (a3), from the viewpoint of improving processability, it is preferably 40% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less, relative to the overall composition of the (meth)acrylic polymer (A).
[0061] The aforementioned “functional group-containing olefinic unsaturated monomers (a4)” can include, for example, monomers containing nitrogen-containing functional groups, carboxyl-containing monomers, acetoacetyl-containing monomers, isocyanate-containing monomers, glycidyl-containing monomers, etc.
[0062] In terms of imparting aggregation force and promoting cross-linking, monomers containing functional groups with nitrogen atoms are preferred, monomers containing amino groups and monomers containing amide groups are more preferred, and monomers containing amino groups are even more preferred.
[0063] Examples of "amino-containing monomers" that are described as "monomers containing functional groups with nitrogen atoms" include (meth)acrylates containing primary amino groups such as (meth)acrylate and (meth)acrylate containing amino ethyl ethyl ester; (meth)acrylates containing secondary amino groups such as (meth)acrylate containing tert-butylaminoethyl ester and (meth)acrylate containing tert-butylaminopropyl ester; (meth)acrylates containing tertiary amino groups such as (meth)acrylate containing ethylaminoethyl ester, (meth)acrylate containing dimethylaminoethyl ester, (meth)acrylate containing diethylaminoethyl ester, (meth)acrylate containing dimethylaminopropyl ester, (meth)acrylate containing diethylaminopropyl ester, and dimethylaminopropylacrylamide; etc.
[0064] Examples of "amide-containing monomers" mentioned above include (meth)acrylamide; N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, N-n-butyl (meth)acrylamide, diacetone (meth)acrylamide, N,N'-methylenebis(meth)acrylamide, and other N-alkyl (meth)acrylamides; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-ethylmethylacrylamide, N,N-diallyl (meth)acrylamide, and other N,N-dialkyl (meth)acrylamides; N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, and other hydroxyalkyl (meth)acrylamides; N-methoxymethyl (meth)acrylamide, N-(n-butoxymethyl)(meth)acrylamide, and other alkoxyalkyl (meth)acrylamides; etc.
[0065] Examples of the aforementioned "carboxyl-containing monomers" include (meth)acrylic acid, (meth)acrylic acid carboxyethyl ester, 2-(meth)acryloyloxyethyl ester of hexahydrophthalic acid, 2-(meth)acryloyloxypropyl ester of hexahydrophthalic acid, 2-(meth)acryloyloxyethyl ester of phthalic acid, 2-(meth)acryloyloxypropyl ester of phthalic acid, 2-(meth)acryloyloxyethyl ester of maleic acid, 2-(meth)acryloyloxypropyl ester of maleic acid, 2-(meth)acryloyloxyethyl ester of succinic acid, 2-(meth)acryloyloxypropyl ester of succinic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, monomethyl maleate, and monomethyl itaconic acid.
[0066] Examples of the aforementioned "acetoacetyl monomers" include 2-(acetoacetoxy)ethyl methacrylate and allyl acetoacetate.
[0067] Examples of the aforementioned "isocyanate-containing monomers" include 2-acryloyloxyethyl isocyanate, 2-methacryloyloxyethyl isocyanate, and their alkyl oxide adducts. The isocyanate group can be protected by end-capping agents such as methyl ethyl ketone oxime, 3,5-dimethylpyrazole, 1,2,4-triazole, and diethyl malonate.
[0068] Examples of "glycidyl monomers" mentioned above include glycidyl (meth)acrylate and allyl (meth)acrylate.
[0069] These functionalized olefinic unsaturated monomers (a4) can be used alone or in combination of two or more.
[0070] From the viewpoint of improving the heat resistance and light resistance of the adhesive composition, the upper limit of the content of the functional group-containing olefinic unsaturated monomer (a4) is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 10% by mass or less, and particularly preferably 5% by mass or less, relative to the overall composition of the (meth)acrylic polymer (A).
[0071] The aforementioned (meth)acrylic polymer (A) may contain other comonomers (a5) as comonomer components as needed.
[0072] Other copolymer monomers (a5) mentioned above include, for example, phenyl methacrylate, benzyl methacrylate, phenoxyethyl methacrylate, diethylene glycol methacrylate, phenoxy polyethylene glycol methacrylate, phenoxy polyethylene glycol-polypropylene glycol-methacrylate, nonylphenol ethylene oxide adduct methacrylate, etc., aromatic (meth)acrylate monomers, 4-acryloyloxybenzophenone, 4-acryloyloxyethoxybenzophenone, 4-acryloyloxy-4'-methoxybenzophenone, 4-acryloyloxyethoxy-4'-methoxybenzophenone, 4-acryloyloxy-4'-bromobenzophenone, 4-acryloyloxyethoxy-4'-bromobenzophenone, 4-methacryloyloxybenzophenone, 4-methylacryloyloxybenzophenone, 4-methyl Acryloyloxyethoxybenzophenone, 4-methacryloyloxy-4'-methoxybenzophenone, 4-methacryloyloxyethoxy-4'-methoxybenzophenone, 4-methacryloyloxy-4'-bromobenzophenone, 4-methacryloyloxyethoxy-4'-bromobenzophenone and mixtures thereof, and other (meth)acrylate monomers with a benzophenone structure, acrylonitrile, methacrylonitrile, styrene, α-methylstyrene, vinyl stearate, vinyl chloride, vinylidene chloride, alkyl vinyl ethers, vinyltoluene, vinylpyridine, vinylpyrrolidone, dialkyl itaconic acid, dialkyl fumarate, allyl alcohol, acryloyl chloride, methyl vinyl ketone, N-acrylamidomethyltrimethylammonium chloride, allyltrimethylammonium chloride, dimethylallyl vinyl ketone, and other vinyl monomers. They can be used alone or in combination of two or more.
[0073] The (meth)acrylic polymer (A) can incorporate photoactive sites, such as polymeric carbon double bonds, into its side chains. Therefore, even without containing polyfunctional (meth)acrylates (D), this adhesive composition I can be crosslinked via free radical polymerization.
[0074] In addition, the crosslinking sensitivity of this adhesive composition I can be improved. This adhesive composition I can be crosslinked by irradiation with lower energy active energy rays, which can impart cohesion and heat resistance.
[0075] As a method for introducing polymeric carbon double bond groups onto the side chain of (meth)acrylic polymer (A), an example can be given as follows: a copolymer containing the above-mentioned hydroxyl-containing monomer (a2) and an olefinic unsaturated monomer (a4) containing a functional group as copolymer components is prepared, and then a compound (a6) having functional groups and polymeric carbon double bond groups that can react with them is subjected to a condensation or addition reaction while maintaining the activity of the polymeric carbon double bond groups.
[0076] Examples of combinations of these functional groups include epoxy (glycidyl) and carboxyl, amino and carboxyl, amino and isocyanate, epoxy (glycidyl) and amino, hydroxyl and epoxy, and hydroxyl and isocyanate. Among these combinations, the combination of hydroxyl and isocyanate is preferred for ease of reaction control. Furthermore, a combination where the copolymer has hydroxyl groups and the aforementioned compound has isocyanate groups is particularly suitable.
[0077] Examples of isocyanate compounds having polymerizable carbon double bond groups include 2-acryloyloxyethyl isocyanate, 2-methacryloyloxyethyl isocyanate, and their epoxide adducts.
[0078] From the viewpoint of improving adhesion and stress relief, the amount of the aforementioned compound (a6) added is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, further preferably 5 parts by mass or less, and particularly preferably 3 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic polymer (A).
[0079] From the viewpoint of obtaining adhesive composition I with high cohesive strength, the mass-average molecular weight of (meth)acrylic polymer (A) is preferably 100,000 or more, more preferably 300,000 or more, and even more preferably 500,000 or more.
[0080] Furthermore, from the viewpoint of obtaining this adhesive composition I with high flowability and stress relief, the upper limit of the mass-average molecular weight of the (meth)acrylic polymer (A) is preferably 2 million or less, more preferably 1.5 million or less, and even more preferably 1 million or less.
[0081] <UV Absorber (B)>
[0082] This adhesive composition I contains an ultraviolet absorber (B), which reduces light-induced degradation of coated polarizing elements.
[0083] It should be noted that this adhesive composition I contains an ultraviolet absorber (B). Therefore, in the case of light curing, it is preferable to cure by light of a wavelength other than the absorption wavelength of the ultraviolet absorber (B).
[0084] Examples of UV absorbers (B) include benzophenone-based UV absorbers containing a benzophenone structure, benzotriazole-based UV absorbers containing a benzotriazole structure, triazine-based UV absorbers containing a triazine structure, salicylic acid-based UV absorbers containing a salicylic acid structure, and cyanoacrylate-based UV absorbers containing a cyanoacrylate structure. These UV absorbers can be used alone or in combination of two or more.
[0085] Examples of benzophenone-based ultraviolet absorbers include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone, 2-hydroxy-4-methoxy-5-sulfonic acid trihydrate benzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sulfonic acid sodium benzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone.
[0086] Examples of benzotriazole-based ultraviolet absorbers include 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazole-2-yl)phenol], and 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole. 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-di-tert-pentylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-4-octoxyphenyl)benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidemethyl)-5-methylphenyl]benzotriazole, etc.
[0087] Examples of triazine-based ultraviolet absorbers include 2-(2-hydroxy-4-methoxyphenyl)-4,6-diphenyl-1,3,5-triazine, 2-(2-hydroxy-4-ethoxyphenyl)-4,6-diphenyl-1,3,5-triazine, 2-(2-hydroxy-4-propoxyphenyl)-4,6-diphenyl-1,3,5-triazine, 2-(2-hydroxy-4-butoxyphenyl)-4,6-diphenyl-1,3,5-triazine, 2-(2-hydroxy-4-hexyloxyphenyl)-4,6-diphenyl-1,3,5-triazine, and 2-(2-hydroxy-4-octyloxyphenyl)- 4,6-Diphenyl-1,3,5-triazine, 2-(2-hydroxy-4-dodecyloxyphenyl)-4,6-diphenyl-1,3,5-triazine, 2-(2-hydroxy-4-benzyloxyphenyl)-4,6-diphenyl-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxy-3-methylphenyl)-1,3,5-triazine, 2-(2-hydroxy-4-[1-octoxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1 3,5-Triazine, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tetrazoloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-(2'-ethylhexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2,4-bis(2,4-dimethylphenyl)- 6-[2-hydroxy-4-(3-octoxy-2-hydroxypropyloxy)-5-α-cumylphenyl]-triazine, 2,4-bis(2,4-dimethylphenyl)-6-[2-hydroxy-4-(3-nonyloxy-2-hydroxypropyloxy)-5-α-cumylphenyl]-triazine, 2,4-bis(2,4-dimethylphenyl)-6-[2-hydroxy-4-(3-decyloxy-2-hydroxypropyloxy)-5-α-cumylphenyl]-triazine, 2-(2-hydroxy-4-acryloyloxyethoxyphenyl)-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, etc.
[0088] Examples of salicylic acid-based ultraviolet absorbers include phenyl salicylate, p-tert-butyl phenyl salicylate, and p-octyl phenyl salicylate.
[0089] Examples of cyanoacrylate-based ultraviolet absorbers include 2-ethylhexyl 2-cyano-3,3'-diphenylacrylate and ethyl 2-cyano-3,3'-diphenylacrylate.
[0090] From the viewpoint of effectively suppressing light reaching coated polarizing elements, benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and triazine-based ultraviolet absorbers are preferred. From the viewpoint of excellent resistance to yellowing, benzophenone-based ultraviolet absorbers containing a benzophenone structure are more preferred.
[0091] Furthermore, from the viewpoint of being able to block light up to the long wavelength region, 2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and sodium benzophenone 2,2'-dihydroxy-4,4'-dimethoxy-5-sulfonate are preferred dihydroxybenzophenone-based ultraviolet absorbers.
[0092] From the viewpoint of improving lightfastness reliability, the lower limit of the content of ultraviolet absorber (B) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, further preferably 1.5 parts by mass or more, particularly preferably 3 parts by mass or more, especially preferably 5 parts by mass or more, and most preferably 6 parts by mass or more, relative to 100 parts by mass of the aforementioned (meth)acrylic polymer (A).
[0093] On the other hand, regarding the upper limit of the content of ultraviolet absorber (B), from the viewpoint of inhibiting exudation and improving resistance to yellowing, it is preferably 15 parts by mass or less, more preferably 12 parts by mass or less, further preferably 10 parts by mass or less, particularly preferably 8 parts by mass or less, and most preferably 7 parts by mass or less, relative to 100 parts by mass of the aforementioned (meth)acrylic polymer (A).
[0094] <Free Radical Polymerization Initiator (C)>
[0095] The free radical polymerization initiator (C) can be any substance that can release free radical polymerization by irradiation with active energy rays such as light or by heat. In particular, photoradiative polymerization initiators that can initiate the reaction by irradiation with active energy rays such as light are preferred in terms of excellent productivity as they do not require curing during solidification.
[0096] Examples of thermal free radical polymerization initiators include organic peroxides such as hydrogen peroxide and perbenzoic acid, and azo compounds such as azobisbutyronitrile.
[0097] On the other hand, photoradical polymerization initiators can be roughly divided into two categories based on the free radical generation mechanism: photo-cracking type photoradical polymerization initiators, which can generate free radicals by breaking down the single bonds of the photoradical polymerization initiator itself; and hydrogen abstraction type photoradical polymerization initiators, which can transfer hydrogen from the hydrogen donor after photoexcitation to form an excited complex with the hydrogen donor in the system.
[0098] The photolytic free radical polymerization initiator decomposes into other compounds when free radicals are generated by light irradiation, and once excited, it loses its function as a reaction initiator. Therefore, no active material remains in the adhesive layer or adhesive sheet after the crosslinking reaction is completed, and there is no possibility of unexpected photodegradation of the adhesive layer or adhesive sheet, so it is preferred.
[0099] On the other hand, hydrogen-abstracting photoradical polymerization initiators can maintain their function as reaction initiators even after repeated light irradiation. Moreover, when free radicals react based on irradiation by active energy rays such as ultraviolet rays, they do not produce decomposition products like those of photodegradation type free radical polymerization initiators. Therefore, they are not easily volatile components after the reaction is completed, which is useful in reducing damage to the adhered material.
[0100] In the above-mentioned photoradical polymerization initiators, from the viewpoint of ensuring the light resistance reliability of the adhesive layer or adhesive sheet, a photodegradation type free radical polymerization initiator is preferably selected in this adhesive composition I.
[0101] When using a photoradical polymerization initiator, from the viewpoint of avoiding reaction obstacles caused by ultraviolet absorber (B), it is preferable to use a visible light initiator that generates free radicals by irradiation with visible light, light with wavelengths of at least 390 nm, 405 nm and 410 nm, such as light in the wavelength range of 380 nm to 700 nm, and becomes the starting point for the crosslinking reaction of this adhesive composition I.
[0102] However, visible light initiators can generate free radicals by exposure to visible light alone, or by exposure to light in wavelength regions outside the visible light region.
[0103] Examples of photolytic radical polymerization initiators include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexylphenyl one, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-(4-(2-hydroxyethoxy)phenyl)-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-[4-{4-(2-hydroxy-2-methyl-propanoyl)benzyl}phenyl]-2-methyl-propane-1-one, and oligomeric (2-hydroxy-2-methyl-1-(4-(1-methylvinyl)phenyl)propane-1-one). ketones), methyl phenylglyoxylate, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl)-1-[4-(4-morpholino)phenyl]-1-butanone, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, (2,4,6-trimethylbenzoyl)ethoxyphenylphosphine oxide, and their derivatives, etc.
[0104] From the perspective of decomposing and decolorizing after the reaction, acylphosphine oxide photoinitiators such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, (2,4,6-trimethylbenzoyl)ethoxyphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)2,4,4-trimethylpentylphosphine oxide are preferred.
[0105] Examples of hydrogen-abstracting photoradical polymerization initiators include bis(2-phenyl-2-oxoacetic acid)oxobis(ethylene), methyl phenylglyoxylate, a mixture of ethyl 2-[2-oxo-2-phenyl-acetoxy-ethoxy] ester and ethyl 2-[2-hydroxy-ethoxy] ester of oxy-phenyl-acetic acid, thioxanthone, 2-chlorothioxanthone, 3-methylthioxanthone, 2,4-dimethylthioxanthone, anthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, camphorquinone, and their derivatives.
[0106] Preferably, it is selected from any one or two of the group consisting of methyl phenylglyoxylate, ethyl 2-[2-oxo-2-phenyl-acetoxy-ethoxy]acetate and ethyl 2-[2-hydroxy-ethoxy]acetate.
[0107] It should be noted that photoradical polymerization initiators are not limited to the substances listed above. Any one of the photoradical polymerization initiators listed above or its derivatives can be used, or a combination of two or more can be used. In addition, visible light initiators can be mixed with substances that generate free radicals solely by irradiation with other light sources such as ultraviolet light.
[0108] The thermal free radical polymerization initiator and the photofree radical polymerization initiator can be used together.
[0109] There is no particular limitation on the content of the free radical polymerization initiator (C). From the viewpoint of ensuring that the polymerization reaction proceeds fully and improving the shape stability of the adhesive sheet, it is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, further preferably 1 part by mass or more, and particularly preferably 2 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic polymer (A).
[0110] Furthermore, regarding the upper limit of the content of the free radical polymerization initiator (C), from the viewpoint of ensuring adhesion, it is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, further preferably 6 parts by mass or less, and particularly preferably 4 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic polymer (A).
[0111] <Polyfunctional (meth)acrylates (D)>
[0112] This adhesive composition I preferably contains, as needed, a polyfunctional (meth)acrylate (D).
[0113] This adhesive composition I, by including a polyfunctional (meth)acrylate (D), forms a cross-linked structure, which imparts cohesiveness and moderate toughness to the adhesive sheet I. Therefore, when manufacturing the coated polarizing element with the adhesive layer described later, it is possible to prevent the surface of the coated polarizing element from bending or the adhesive layer from deforming and cracking during cutting.
[0114] Multifunctional (meth)acrylate (D) is a compound or composition that forms a cross-linked structure in this adhesive composition I. Examples include (meth)acrylate monomers and (meth)acrylate oligomers having two or more functional groups.
[0115] Examples of (meth)acrylate monomers include 1,4-butanediol di(meth)acrylate, glycerol di(meth)acrylate, neopentyl glycol di(meth)acrylate, glycerol glycidyl ether di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, tricyclodecane dimethacrylate, tricyclodecanediethanol di(meth)acrylate, bisphenol A polyethoxydi(meth)acrylate, bisphenol A polypropoxydi(meth)acrylate, bisphenol F polyethoxydi(meth)acrylate, ethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane trioxyethyl(meth)acrylate, ε-caprolactone-modified tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, and ethoxylated tri(meth)acrylate. The following are listed: oxy-based pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, tri(acryloyloxyethyl)isocyanurate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol penta(meth)acrylate, neopentyl glycol di(meth)acrylate of hydroxypentaerythritol, di(meth)acrylate of ε-caprolactone adduct of pentyl glycol hydroxypentaerythritol, trimethylolpropane tri(meth)acrylate, trimethylolpropane polyethoxytri(meth)acrylate, di(trimethylolpropane tetra(meth)acrylate, etc.
[0116] From the viewpoint of imparting appropriate toughness to the cured material, (meth)acrylic monomers are preferred, and more preferably, polyfunctional (meth)acrylic monomers with an alkylene glycol backbone, such as polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate.
[0117] For the molecular weight of (meth)acrylic acid monomers, from the viewpoint of imparting appropriate flexibility to the cured product, a molecular weight of 200 or more is preferred, more preferably 300 or more, further preferably 400 or more, and particularly preferably 500 or more is preferred. It should be noted that the upper limit of the above molecular weight is generally 3000 or less, and preferably 2000 or less.
[0118] Examples of (meth)acrylic oligomers include polyfunctional (meth)acrylic oligomers such as polyester (meth)acrylates, epoxy (meth)acrylates, urethane (meth)acrylates, and polyether (meth)acrylates.
[0119] From the viewpoint of imparting appropriate toughness to the cured product, urethane (meth)acrylate oligomers are preferred.
[0120] Furthermore, when this adhesive composition I is cured, a cured product with high toughness can be obtained. In other words, from the viewpoint of obtaining a cured product with moderate flexibility, the polyfunctional (meth)acrylate (D) is preferably a (meth)acrylate oligomer with a molecular weight of 3000 or more, and particularly preferably a polyfunctional (meth)acrylate with a molecular weight of 5000 or more, 8000 or more, or 10000 or more. It should be noted that the upper limit of the above molecular weight is generally 100000 or less, and preferably 50000 or less.
[0121] From the viewpoint of the shape stability of the adhesive sheet and the ability to impart durability when forming a laminate from the adhesive sheet, the content of the polyfunctional (meth)acrylate (D) is preferably 1 part by mass or more, more preferably 2 parts by mass or more, further preferably 5 parts by mass or more, and particularly preferably 10 parts by mass or more, relative to 100 parts by mass of the (meth)acrylate polymer (A).
[0122] Regarding the upper limit of the mass of the polyfunctional (meth)acrylate (D), from the viewpoint of ensuring adhesion, it is preferably 100 parts by mass or less, more preferably 60 parts by mass or less, further preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less, relative to 100 parts by mass of the (meth)acrylate polymer (A).
[0123] <Other Ingredients>
[0124] This adhesive composition I may contain, as needed, various additives such as tackifying resins, antioxidants, light stabilizers, metal deactivators, anti-aging agents, hygroscopic agents, rust inhibitors, silane coupling agents, inorganic particles, etc., as "other ingredients".
[0125] In addition, depending on the requirements, reaction catalysts containing tertiary amine compounds, quaternary ammonium compounds, tin lauryl compounds, etc., may also be used.
[0126] <Curing properties>
[0127] This adhesive composition I can be cured in one step, or it can be cured in multiple stages. That is, it can be cured with room for further curing. In terms of gel rate, the gel rate of this adhesive composition I can be 60% or more in one curing, or the gel rate can be set to 20-60% in the first curing, leaving room for further curing.
[0128] For example, when the adhesive composition I has the property of curing with active energy rays, after being laminated with components of an image display device such as a coated polarizing element, or after forming a laminate with a coated polarizing element and other components of an image display device, the adhesive composition I is cured by irradiation with light, thereby making the coated polarizing element and other components of the image display device more firmly bonded, thus improving the reliability of the laminate.
[0129] From the perspective of suppressing damage to the components of the image display device and controlling the reaction, ultraviolet and visible light are suitable light sources.
[0130] There are no particular limitations on the irradiation time or method, but it is preferable to irradiate from the opposite side of the laminated surface of the components constituting the image display device, such as the coated polarizing element.
[0131] Furthermore, there are no particular restrictions on the irradiation energy, irradiation time, or irradiation method of the active energy rays, as long as they can activate the initiator and polymerize the (meth)acrylate component.
[0132] <Light transmittance>
[0133] From the viewpoint of preventing light degradation of the coated polarizing element when the adhesive layer formed by the adhesive composition I is used in combination with the coated polarizing element, the transmittance of the 50 μm thick adhesive layer formed by the adhesive composition I at a wavelength of 400 nm is preferably 50% or less, more preferably 40% or less, further preferably 30% or less, and particularly preferably 25% or less.
[0134] Furthermore, for this adhesive composition I, from the viewpoint of preventing light degradation of the coated polarizing element when the adhesive layer formed by this adhesive composition I is used in combination with the coated polarizing element, the transmittance of the 50 μm thick adhesive layer formed by this adhesive composition I at a wavelength of 380 nm is preferably less than 20%, more preferably less than 5%, further preferably less than 2%, and particularly preferably less than 1%.
[0135] Furthermore, from the viewpoint of ensuring sufficient image visibility when the adhesive layer formed by the adhesive composition I is used in an image display device, the transmittance of the 50 μm thick adhesive layer formed by the adhesive composition I at a wavelength of 430 nm is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, particularly preferably 80% or more, and especially preferably 85% or more.
[0136] <<This adhesive sheet I>>
[0137] An example of an embodiment of the present invention is an adhesive sheet I for a coated polarizing element (referred to as "the adhesive sheet I") which includes an adhesive layer I (referred to as "the adhesive layer I") formed using the adhesive composition I.
[0138] The adhesive sheet I can be a single layer consisting of an adhesive layer formed using the adhesive composition I, or it can be a multilayer consisting of two or more layers other than the adhesive layer.
[0139] When this adhesive sheet I is a multilayer structure with two or more layers, the composition of the layers other than those formed by this adhesive composition I is arbitrary. However, for example, when the layers other than this adhesive layer I form the intermediate layer, the outermost layer, or the innermost layer, from the viewpoint of further improving interlayer adhesion, the adhesive composition forming the layers other than this adhesive layer I is preferably formed of an adhesive composition containing a (meth)acrylic polymer as the main component resin, and more preferably containing the same (meth)acrylic polymer (A) as this adhesive layer I as the main component resin. Furthermore, the layers other than this adhesive layer I also more preferably contain a multifunctional (meth)acrylic ester and a free radical polymerization initiator.
[0140] When this adhesive sheet I is composed of two or more layers, it is preferable that at least the outermost layer, the innermost layer, or two of them are equivalent to this adhesive layer. Alternatively, all layers may be equivalent to this adhesive layer.
[0141] When the adhesive sheet I is composed of two or more layers, the thickness of the adhesive layer relative to the overall thickness of the adhesive sheet I is preferably 10% or more and 100% or less, wherein a ratio of 14% or more or 70% or less, and wherein a ratio of 20% or more or 50% or less is further preferred.
[0142] (Light transmittance)
[0143] From the viewpoint of preventing light degradation of the coated polarizing element when used in combination with the coated polarizing element, the transmittance at a wavelength of 400 nm is preferably 50% or less, more preferably 40% or less, further preferably 30% or less, and particularly preferably 25% or less.
[0144] Furthermore, for this adhesive layer I or this adhesive sheet I, from the viewpoint of preventing light degradation of the coated polarizing element when used in combination with the coated polarizing element, the transmittance at a wavelength of 380 nm is preferably less than 20%, more preferably less than 5%, further preferably less than 2%, and particularly preferably less than 1%.
[0145] Furthermore, from the viewpoint of ensuring sufficient image visibility when used in an image display device, the transmittance at a wavelength of 430 nm is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, particularly preferably 80% or more, and especially preferably 85% or more.
[0146] (b* value)
[0147] From the viewpoint that the adhesive layer I or the adhesive sheet I can suppress adverse effects on image quality when used in an image display device, the b* value is preferably 10 or less, more preferably 5 or less, further preferably 3 or less, and particularly preferably 2 or less.
[0148] The above b* value is the value of b* in the color space represented by L*a*b* as specified in JIS Z8781-4. It means that if the value is increased on the positive side, the color becomes more yellow; if the value is increased on the negative side, the color becomes more blue; and if the value is close to 0, the color becomes achromatic.
[0149] In this adhesive layer I or adhesive sheet I, in order to adjust the transmittance and b* value at wavelengths of 380 nm, 400 nm, and 430 nm to the aforementioned ranges, it is preferable to adjust the type and amount of ultraviolet absorber to a suitable range. However, this method is not limited to this.
[0150] In addition, for this adhesive layer I or this adhesive sheet I, the transmittance T(380) at a wavelength of 380 nm, the transmittance T(430) at a wavelength of 430 nm and the b* value preferably satisfy the relationship of the following equations (I) and (II).
[0151] 0≤T(380)×b*≤50 (I)
[0152] 70≤T(430)×b*≤220 (II)
[0153] By satisfying the relationship between the above formulas (I) and (II), this adhesive layer I or this adhesive sheet I can achieve a higher level of balance between preventing light degradation of coated polarizing elements and image visibility of image display devices.
[0154] Based on the above viewpoint, T(380)×b* in the above formula (I) is preferably 0 to 50, more preferably 0 to 40, further preferably 0 to 30, and especially preferably 0 to 20.
[0155] In the above formula (II), T(430)×b* is preferably 70 to 220, more preferably 80 or more or 210 or less, further preferably 90 or more or 200 or less, and particularly preferably 100 or more or 190 or less.
[0156] (Gel ratio)
[0157] The gel rate of this adhesive layer I or this adhesive sheet I is preferably 20% or more when used in attachment. A gel rate of 20% or more provides the adhesive sheet with shape stability and durability when forming a laminate.
[0158] Based on the above viewpoint, the gelation rate of the adhesive layer I or the adhesive sheet I is more preferably 40% or more, further preferably 50% or more, and particularly preferably 60% or more.
[0159] On the other hand, if the gelation rate is 95% or less, even if the adhered material is a component with a height difference on its surface, no strain or deformation will occur in the component, and it can fill in all places following the height difference. From the above point of view, it is preferable to be 95% or less, more preferably 85% or less, further preferably 80% or less, and particularly preferably 75% or less.
[0160] In order to adjust the gel rate to the above-mentioned range during application in this adhesive layer I or adhesive sheet I, it is preferable to adjust the composition and molecular weight of the (meth)acrylate polymer (A), or adjust the amount of polyfunctional (meth)acrylate (D) and free radical polymerization initiator (C), or adjust the intensity and cumulative light intensity of the irradiated active energy rays. However, this method is not limited to these means.
[0161] (thickness)
[0162] Regarding the thickness of this adhesive layer I or this adhesive sheet I, from the viewpoint of protecting the coated polarizing element, it is preferably 10 μm or more, more preferably 20 μm or more, further preferably 30 μm or more, and particularly preferably 40 μm or more. On the other hand, regarding the upper limit of the thickness, from the viewpoint of facilitating the thinning of the image display device, it is preferably 175 μm or less, more preferably 120 μm or less, further preferably 80 μm or less, and particularly preferably 60 μm or less.
[0163] <Manufacturing Method of Adhesive Sheet I>
[0164] Next, the manufacturing method of this adhesive sheet I will be described. However, the following description is only one example of the manufacturing method of this adhesive sheet I, and this adhesive sheet I is not limited to those manufactured by the above-described manufacturing method.
[0165] In the preparation of this adhesive sheet I, in addition to the (meth)acrylic polymer (A), ultraviolet absorber (B), and free radical polymerization initiator (C), a specified amount of polyfunctional (meth)acrylate (D) and further, as needed, "other" components are mixed to prepare this adhesive composition I. This adhesive composition I is then molded into a sheet, and the curable compound is crosslinked, i.e., polymerized and cured as needed, to produce this adhesive sheet I. However, this method is not limited to this.
[0166] When preparing this adhesive composition I, the above raw materials can be mixed using a temperature-controlled mixer (e.g., a single-screw extruder, a twin-screw extruder, a planetary mixer, a twin-screw blender, a pressure kneader, etc.).
[0167] It should be noted that when mixing various raw materials, various additives can be pre-mixed with the resin and then supplied to the mixer, or all materials can be pre-melted and mixed before being supplied, or a masterbatch can be made by pre-concentrating the additives in the resin and then supplied.
[0168] As a method for molding the adhesive composition I into a sheet, known methods can be used, such as wet lamination, dry lamination, extrusion casting using a T-die, extrusion lamination, calendering, blow molding, injection molding, and liquid-curing. Among these, wet lamination, extrusion casting, and extrusion lamination are suitable for manufacturing sheets.
[0169] Furthermore, when this adhesive composition I contains a free radical polymerization initiator (C), a cured product can be manufactured by irradiating it with heat and / or active energy rays and then curing it. In particular, this adhesive sheet I can be manufactured by irradiating the adhesive composition I into a molded body, such as a sheet, with heat and / or active energy rays.
[0170] Here, active energy rays used for irradiation can include ionizing radiation such as alpha rays, beta rays, gamma rays, neutron beams, and electron beams, as well as ultraviolet rays and visible light. From the perspective of suppressing damage to the components of optical devices and controlling the reaction, ultraviolet rays and visible light are suitable.
[0171] Furthermore, there are no particular restrictions on the irradiation energy, irradiation time, or irradiation method of the active energy rays, as long as they can activate the initiator and polymerize the (meth)acrylate component.
[0172] In addition, as another embodiment of the manufacturing method of this adhesive sheet I, the adhesive composition I can also be dissolved in a suitable solvent and applied using various coating methods.
[0173] In the case of using a coating method, in addition to curing by irradiation with active energy rays as described above, thermal curing is also performed, thereby obtaining this adhesive sheet I.
[0174] In the case of coating, the thickness of this adhesive sheet I can be adjusted according to the coating thickness and the concentration of solid components in the coating liquid.
[0175] <<This adhesive composition II>>
[0176] An example of an embodiment of the present invention is an adhesive sheet II for a component of an image display device (referred to as "the adhesive sheet II") formed from an adhesive composition II (referred to as "the adhesive composition II") comprising a (meth)acrylic copolymer (A), a hydroxyl-containing benzophenone compound (B1), and a free radical polymerization initiator (C).
[0177] Here, the "image display device components" in the adhesive sheet II for image display device components may include, for example, a reflective sheet, a light guide plate and light source, a diffusion film, a prism sheet, a liquid crystal panel, a phase retardation plate, a glass substrate, a polarizing plate, an organic EL panel, electrodes, an anti-reflective film, a color filter, a touch sensor, a glass cover, a plastic cover, or two or more of these components integrated together. However, it is not limited to these.
[0178] This adhesive composition II, as described below, can be cured by heat or by active energy rays. In particular, curing by active energy rays is preferred where no curing is required and productivity is excellent.
[0179] This adhesive composition II, as described below, can be cured in multiple stages.
[0180] Furthermore, when curing by active energy rays, in the case of adhesive sheets containing ultraviolet absorbers, the ultraviolet absorbers hinder curing under active energy rays. Therefore, it is usually difficult to use active energy ray curing systems. However, this invention dares to apply it, and as a result, a good adhesive sheet can be obtained.
[0181] <(Meth)acrylic polymers (A)>
[0182] For the (meth)acrylic polymer (A) and its content in adhesive composition II, the above description of the (meth)acrylic polymer (A) in adhesive composition I is used. Here, adhesive composition I is replaced with adhesive composition II for reference.
[0183] <Hydroxy-containing benzophenone compounds (B1)>
[0184] This adhesive composition II contains a hydroxyl-containing benzophenone compound (B1) as a UV absorber, thereby ensuring the light resistance reliability of the adhesive sheet itself and reducing the degradation caused by light on the components of the image display device.
[0185] It should be noted that this adhesive composition II contains a hydroxyl-containing benzophenone compound (B1). Therefore, in the case of light curing, it is preferable to cure by light of a wavelength other than that absorbed by the hydroxyl-containing benzophenone compound (B1) which has ultraviolet absorption properties.
[0186] Examples of hydroxyl-containing benzophenone compounds (B1) include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfonic acid benzophenone, 2-hydroxy-4-methoxy-5-sulfonic acid trihydrate benzophenone, and 2,2'-dihydroxy-4-methoxy Benzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, sodium 2,2'-dihydroxy-4,4'-dimethoxy-5-sulfonate benzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, etc.
[0187] Furthermore, from the viewpoint of being able to block light up to the long wavelength region, dihydroxybenzophenone compounds such as 2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and sodium benzophenone sulfonate are further preferred.
[0188] From the viewpoint of improving lightfastness reliability, the lower limit of the content of hydroxyl-containing benzophenone compound (B1) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1.5 parts by mass or more, even more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 6 parts by mass or more, relative to 100 parts by mass of the aforementioned (meth)acrylic polymer (A).
[0189] On the other hand, regarding the upper limit of the content of hydroxyl-containing benzophenone compounds (B1), from the viewpoint of inhibiting exudation and improving resistance to yellowing, it is preferably 15 parts by mass or less, more preferably 12 parts by mass or less, further preferably 10 parts by mass or less, particularly preferably 8 parts by mass or less, and most preferably 7 parts by mass or less, relative to 100 parts by mass of the aforementioned (meth)acrylic polymer (A).
[0190] <Free Radical Polymerization Initiator (C)>
[0191] Regarding the free radical polymerization initiator (C) and its content in this adhesive composition II, the description of the free radical polymerization initiator (C) in this adhesive composition I is used. In this case, this adhesive composition I is replaced with this adhesive composition II, and the ultraviolet absorber (B) is replaced with a hydroxyl-containing benzophenone compound (B1).
[0192] It should be noted that, from the viewpoint of avoiding reaction barriers caused by hydroxyl-containing benzophenone compounds (B1) and suppressing the coloring of the adhesive sheet II caused by the free radical polymerization initiator (C) itself, the aforementioned free radical polymerization initiator (C) of this adhesive composition II preferably has a large absorption at least at a wavelength of 400 to 430 nm.
[0193] Maximum absorption refers to the wavelength at which the absorbance is greatest in the absorption spectrum.
[0194] Furthermore, from the viewpoint of ensuring a balance between the light resistance reliability and shape stability of the adhesive sheet II itself, the mass ratio of the aforementioned hydroxyl-containing benzophenone compound (B1) to the aforementioned free radical polymerization initiator (C) is preferably (B1):(C) = 1:0.05 to 1:20, more preferably 1:0.1 to 1:10, and even more preferably 1:0.3 to 1:2.
[0195] <Polyfunctional (meth)acrylates (D)>
[0196] This adhesive composition II preferably contains, as needed, a polyfunctional (meth)acrylate (D).
[0197] This adhesive composition II, by including a polyfunctional (meth)acrylate (D), forms a cross-linked structure, which imparts cohesiveness and moderate toughness to the adhesive sheet II. Because of its moderate toughness, this adhesive sheet II can prevent surface bending of the image display device component or deformation and cracking of the adhesive layer during cutting when manufacturing the image display device component with the adhesive layer described later.
[0198] Regarding the polyfunctional (meth)acrylate (D) and its content in adhesive composition II, the above description of the polyfunctional (meth)acrylate (D) in adhesive composition I is used as a reference. Here, adhesive composition I is replaced with adhesive composition II for reference only.
[0199] <Other Ingredients>
[0200] This adhesive composition II may, as needed, contain various additives such as tackifying resins, antioxidants, light stabilizers, metal deactivators, anti-aging agents, hygroscopic agents, rust inhibitors, silane coupling agents, and inorganic particles as "other ingredients".
[0201] In addition, depending on the requirements, reaction catalysts containing tertiary amine compounds, quaternary ammonium compounds, tin lauryl compounds, etc., may also be used.
[0202] <Curing properties>
[0203] Regarding the curing properties of this adhesive composition II, the above description regarding the curing properties of this adhesive composition I is used as a reference. Here, adhesive composition I is replaced with adhesive composition II for reference only.
[0204] <Light transmittance>
[0205] From the viewpoint of preventing light degradation of the image display device components when the adhesive layer formed by the adhesive composition II is used in combination with the image display device components, the transmittance of the 50 μm thick adhesive layer formed by the adhesive composition II at a wavelength of 400 nm is preferably less than 30%, more preferably less than 25%, further preferably less than 22%, and particularly preferably less than 20%.
[0206] Furthermore, regarding this adhesive composition II, from the viewpoint of preventing light degradation of the image display device component when the adhesive layer formed by this adhesive composition II is used in combination with the image display device component, the transmittance of the 50 μm thick adhesive layer formed by this adhesive composition II at a wavelength of 380 nm is preferably less than 20%, more preferably less than 5%, further preferably less than 2%, and particularly preferably less than 1%.
[0207] Furthermore, from the viewpoint of ensuring sufficient image visibility when the adhesive layer formed by the adhesive composition II is used in an image display device, the transmittance of the 50 μm thick adhesive layer formed by the adhesive composition II at a wavelength of 430 nm is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, particularly preferably 80% or more, and especially preferably 85% or more.
[0208] <<Adhesive Sheet II>>
[0209] An example of an embodiment of the present invention is an adhesive sheet II for an image display device component (referred to as "the adhesive sheet II") that includes an adhesive layer II (referred to as "the adhesive layer II") formed using the adhesive composition II.
[0210] This adhesive sheet II may be a single layer consisting of an adhesive layer formed using this adhesive composition II, or it may be a multilayer consisting of two or more layers having layers other than the adhesive layer.
[0211] When this adhesive sheet II is a multilayer structure with two or more layers, the composition of the layers other than those formed by this adhesive composition II is arbitrary. However, for example, when the layers other than this adhesive layer II form the intermediate layer, the outermost layer, or the innermost layer, from the viewpoint of further improving interlayer adhesion, the adhesive composition forming the layers other than this adhesive layer II is preferably formed of an adhesive composition containing a (meth)acrylate polymer as the main component resin, and more preferably containing the same (meth)acrylate polymer (A) as this adhesive layer II as the main component resin. Furthermore, the layers other than this adhesive layer II also more preferably contain a multifunctional (meth)acrylate and a free radical polymerization initiator.
[0212] When this adhesive sheet II is composed of two or more layers, it is preferable that at least the outermost layer, the innermost layer, or two of them are equivalent to this adhesive layer. Alternatively, all layers may be equivalent to this adhesive II layer.
[0213] When the adhesive sheet II is composed of two or more layers, the thickness of the adhesive layer II relative to the overall thickness of the adhesive sheet is preferably 10% or more and 100% or less, and more preferably 14% or more or 70% or less, and 20% or more or 50% or less.
[0214] (Light transmittance)
[0215] From the viewpoint of preventing light degradation of the image display device components when used in combination with the image display device components, the transmittance at a wavelength of 400 nm is preferably less than 30%, more preferably less than 25%, further preferably less than 22%, and particularly preferably less than 20%.
[0216] Furthermore, from the viewpoint of preventing light degradation of the image display device constituent components when used in combination with the image display device constituent components, the transmittance at a wavelength of 380 nm is preferably less than 20%, more preferably less than 5%, further preferably less than 2%, and particularly preferably less than 1%.
[0217] Furthermore, from the viewpoint of ensuring sufficient image visibility when used in an image display device, the transmittance at a wavelength of 430 nm is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, particularly preferably 80% or more, and especially preferably 85% or more.
[0218] (b* value)
[0219] From the viewpoint that it can suppress adverse effects on image quality when used in an image display device, the b* value is preferably 3.0 or less, more preferably 2.5 or less, even more preferably 2.0 or less, and particularly preferably 1.8 or less for this adhesive layer II or adhesive sheet II.
[0220] The above b* value is the value of b* in the color space represented by L*a*b* as specified in JIS Z8781-4. It means that if the value is increased on the positive side, the color becomes more yellow; if the value is increased on the negative side, the color becomes more blue; and if the value is close to 0, the color becomes achromatic.
[0221] In addition, for this adhesive layer II or this adhesive sheet II, the transmittance T(380) at a wavelength of 380 nm, the transmittance T(430) at a wavelength of 430 nm and the b* value preferably satisfy the relationship of the following formulas (I) and (II).
[0222] 0≤T(380)×b*≤50 (I)
[0223] 70≤T(430)×b*≤220 (II)
[0224] This adhesive layer II or this adhesive sheet II satisfies the relationship between the above formulas (I) and (II), thereby achieving a higher level of balance between preventing light degradation of the components of the image display device and the image visibility of the image display device.
[0225] Based on the above viewpoint, T(380)×b* in the above formula (I) is preferably 0 to 50, more preferably 0 to 40, further preferably 0 to 30, and especially preferably 0 to 20.
[0226] In the above formula (II), T(430)×b* is preferably 70 to 220, more preferably 80 or more or 210 or less, further preferably 90 or more or 200 or less, and particularly preferably 100 or more or 190 or less.
[0227] In order to adjust the transmittance and b* value at wavelengths of 380 nm, 400 nm, and 430 nm to the aforementioned ranges in this adhesive layer II or adhesive sheet II, it is preferable to adjust the type and amount of hydroxyl-containing benzophenone compound (B1). However, this method is not limited to this.
[0228] (Gel ratio)
[0229] Regarding the gel rate of adhesive layer II or adhesive sheet II, the above description regarding the gel rate of adhesive layer I or adhesive sheet I is used. Here, adhesive layer I or adhesive sheet I is replaced with adhesive layer II or adhesive sheet II for reference only.
[0230] (thickness)
[0231] Regarding the thickness of adhesive layer II or adhesive sheet II, the above description regarding the thickness of adhesive layer I or adhesive sheet I is used. Here, adhesive layer I or adhesive sheet I is replaced with adhesive layer II or adhesive sheet II, and the coating-type polarizing element is replaced with a component for an image display device.
[0232] <Method for manufacturing this adhesive sheet II>
[0233] For the manufacturing method of this adhesive sheet II, the above description of the manufacturing method of this adhesive sheet I is used. Here, adhesive composition I is replaced with adhesive composition II, adhesive sheet I is replaced with adhesive sheet II, coating-type polarizing element is replaced with a component for an image display device, and ultraviolet absorber (B) is replaced with a hydroxyl-containing benzophenone compound (B1).
[0234] <<Adhesive sheet with release film>>
[0235] These adhesive sheets I and II can also be formed into an adhesive sheet with a release film, which is composed of an adhesive sheet I or II stacked with a release film (referred to as "this adhesive sheet with a release film").
[0236] For example, the adhesive sheet with the release film can also be formed by molding a single or multiple sheet-like adhesive layer containing a layer formed by adhesive composition I or II onto the release film (see reference). Figure 6 ).
[0237] As the material for the aforementioned release film, a known release film can be used.
[0238] As a material for release films, it can be suitable for coating silicone resin onto films such as polyester film, polyolefin film, polycarbonate film, polystyrene film, acrylic film, cellulose triacetate film, and fluoropolymer film, and then releasing them, as well as release paper.
[0239] The aforementioned film may have an antistatic layer, a hard coating layer, an anchoring layer, or other layers as needed.
[0240] In the case of a release film being laminated on both sides of this adhesive sheet I or II, one release film may have the same laminated structure or material as the other release film, or it may have a different laminated structure or material.
[0241] Alternatively, it can be the same thickness or different thicknesses.
[0242] In addition, release films with different peel strengths and different thicknesses can be stacked on both sides of this adhesive sheet I or II.
[0243] There is no particular limitation on the thickness of the release film. However, from the viewpoint of processability and operability, a thickness of 12 μm to 250 μm is preferred, with 25 μm or more or 200 μm or less being more preferred, and 38 μm or more or 188 μm or less being more preferred.
[0244] It should be noted that adhesive sheets I and II may also be formed without using the substrate or release film as described above, and by methods such as directly extruding the adhesive composition I or II or by injection into a mold.
[0245] Furthermore, adhesive sheets I and II can also be formed by directly filling the constituent components of the image display device, which are the adhered objects, with the adhesive composition I or II.
[0246] <<This layer of laminated film>>
[0247] As an example of an embodiment of the present invention, the laminate (referred to as "this laminate") has a resin sheet or thin film glass (see reference 1 or 2) on at least one side of this adhesive sheet I or II. Figure 7 ).
[0248] As an example of the aforementioned resin sheet, a resin sheet may be provided in which one or more resins selected from the group consisting of cyclic olefin resins, cellulose triacetate resins, polymethyl methacrylate resins, epoxy resins, polyester resins and polyimide resins are used as the main component resins.
[0249] At this point, the main component resin refers to the resin with the highest mass percentage among the resins constituting the resin sheet, which is the resin that accounts for more than 50% by mass, more than 60% by mass, more than 70% by mass, more than 80% by mass, more than 90% by mass, or more than 95% by mass (including 100% by mass) of the resin constituting the resin sheet.
[0250] Examples of thin-film glass include ultra-thin sheet glass (G-Leaf, manufactured by Nippon Electric Glass Co., Ltd.) and other glass with bend resistance.
[0251] <<This coated polarizing element with adhesive layer>>
[0252] As an example of an embodiment of the present invention, a coated polarizing element with an adhesive layer (referred to as "this coated polarizing element with an adhesive layer") is a coated polarizing element having an adhesive layer I (referred to as "this adhesive layer I") or an adhesive sheet I formed from the adhesive composition I on at least one side of the coated polarizing element.
[0253] This coated polarizing element with an adhesive layer can also be, for example, an adhesive sheet with a polarizing element having a coated polarizing element on at least one side of the adhesive sheet I.
[0254] The adhesive sheet with polarizing element can be manufactured, for example, by: forming the polarizing element on a substrate with release properties and then transferring the polarizing element to the surface of the adhesive sheet I; directly molding the adhesive sheet I onto a coated polarizing element; forming a coated polarizing element on the adhesive sheet I; etc.
[0255] In addition, this coated polarizing element with adhesive layer can be a coated polarizing element having an adhesive layer on at least one side of the adhesive layer I.
[0256] At this time, the aforementioned adhesive layer I can be directly applied to the coated polarizing element, or the adhesive layer formed by the adhesive composition I can be formed on other substrates and then transferred to the coated polarizing element.
[0257] Furthermore, this coated polarizing element with adhesive layer can be a structure formed by directly laminating the coated polarizing element with this adhesive layer I or this adhesive sheet I, or it can have other components sandwiched between them. All of these configurations can benefit from the effects of this invention.
[0258] At this point, examples of "other components" include reflective sheets, light guide plates and light sources, diffusion films, prism sheets, liquid crystal panels, organic EL panels, anti-reflective films, color filters, polarizing plates, phase difference plates, glass substrates, glass covers, plastic covers, or composites of two or more of these components.
[0259] <Coated polarizing element>
[0260] The aforementioned coated polarizing element, as described above, is a laminate comprising a film formed by coating an optically anisotropic composition containing a liquid crystal compound. For example, an optically anisotropic composition containing a liquid crystal compound is coated onto an alignment film formed on a substrate, aligning the optically anisotropic composition, and then cured in the aligned state to form an optically anisotropic layer. Various optically anisotropic components can then be fabricated using the optically anisotropic layer with the substrate, or an optically anisotropic layer peeled off from the substrate. The optically anisotropic component may have an optically anisotropic layer formed from the optically anisotropic composition and an alignment film. Alternatively, it may only have an optically anisotropic layer without an alignment film.
[0261] Examples of liquid crystal compounds include polymeric liquid crystal compounds, high molecular weight liquid crystal compounds, and lyotropic liquid crystal compounds.
[0262] Existing polarizing plates typically have the following structure: an adhesive is applied to a structure consisting of a polyvinyl alcohol (PVA) film sandwiched between a protective film such as a TAC (cellulose triacetate) film, or laminated adhesive sheets.
[0263] However, if a polarizing plate is used that employs an optical anisotropic layer formed from a coated polarizing element, the film can be formed by coating, thus reducing the thickness compared to existing polarizing elements.
[0264] In addition, existing retardation plates are usually obtained by stretching resin sheets such as polycarbonate, but if they are too thin, they are prone to breakage, thus limiting their thin-film production.
[0265] However, if a phase retardation plate using an optical anisotropic layer formed by a coated polarizing element is to be used, it is easier to thin compared to existing stretched sheets, and therefore the thickness can be reduced.
[0266] By using such a polarizing plate formed by a coated polarizing element and / or a circular polarizing plate using a phase retardation plate in an image display device, it is possible to facilitate the thin-film transformation of the image display device.
[0267] Examples of "substrate" used to form coated polarizing elements include resin sheets or glass with one or more resins selected from the group consisting of polyolefin resins, cyclic polyolefin resins, polyester resins, poly(meth)acrylate resins, cellulose ester resins, polycarbonate resins, and polyimide resins as the main component. Other layers may be applied to the substrate as needed, such as antistatic layers, hard coatings, anchoring layers, release layers, easy-to-bond layers, protective layers, anti-bleeding color layers, and planarization layers.
[0268] To align liquid crystal compounds, methods can be employed that utilize alignment-confining forces generated by alignment films disposed on a substrate, alignment-confining forces generated by external fields such as electric fields and magnetic fields, and / or shear forces during coating. From the viewpoint of achieving a highly ordered alignment state of the polymerizable liquid crystal compound and obtaining a coated polarizing element exhibiting excellent optical performance, methods based on alignment films are particularly preferred.
[0269] The alignment film disposed on the substrate is a layer having an alignment constraint force that orients the polymeric liquid crystal compound (described later) in a desired direction. Preferably, the alignment film has solvent resistance that prevents dissolution when coated with an optically anisotropic composition solution, moderate solution affinity that does not repel the optically anisotropic composition solution, and heat resistance during solvent drying and heat treatment during liquid crystal alignment.
[0270] Alignment films can undergo alignment processing to control the alignment direction. Examples of alignment processing methods include those described in "Liquid Crystal Handbook" (published by Maruzen Co., Ltd. on October 30, 2013), pages 226-239, such as brushing, forming grooves (fine groove structures) on the surface of the alignment film, using polarized ultraviolet light / polarized laser (photoalignment), alignment methods based on LB film formation, and alignment methods based on tilted evaporation of inorganic materials. From the viewpoint of easily obtaining high alignment degrees, brushing and photoalignment are particularly preferred.
[0271] The thickness of the alignment film is typically 10 nm to 1000 nm, preferably 50 nm to 800 nm. By using the aforementioned range, sufficient alignment confinement force required for aligning the polymeric liquid crystal compound and thin film formation can be achieved.
[0272] Optical anisotropic compositions can be compositions containing, in addition to liquid crystal compounds, polymerization initiators, polymerization inhibitors as needed, polymerization aids, polymerizable non-liquid crystal compounds, surfactants, leveling agents, coupling agents, pH adjusters, dispersants, antioxidants, organic / inorganic fillers, metal oxides, and various other additives and solvents. The cured layer of this composition functions as an optical polarization element.
[0273] When the polarizing element is a polarizing film, it is preferable that the optically anisotropic composition contains a dichroic pigment. Examples of dichroic pigments include iodine and dichroic organic dyes. The dichroic pigment used can be a single pigment or a combination of multiple different pigments.
[0274] The aforementioned dichroic organic dyes are not particularly limited and can include azo dyes, quinone dyes (including naphthoquinone dyes, anthraquinone dyes, etc.), violet dyes, anthocyanin dyes, phthalocyanine dyes, indigo dyes, and fused polycyclic dyes (including perylene dyes, oxazine dyes, acridine dyes, etc.). Among these dyes, azo dyes are preferred because they have a large molecular length-to-short axis ratio and exhibit good dichroism.
[0275] (polymeric liquid crystal compound)
[0276] The aforementioned polymerizable liquid crystal compound is a liquid crystal compound possessing polymerizable functional groups, combining the properties of a polymerizable monomer and a liquid crystal. Therefore, by crosslinking the polymerizable functional groups while maintaining the liquid crystal orientation, the orientation can be fixed, exhibiting optical anisotropy. The polymerizable liquid crystal compound used can be a single compound or a combination of compounds with different structures.
[0277] The polymerizable liquid crystal compound can be any of a low-molecular-weight liquid crystal compound having polymerizable functional groups or a high-molecular-weight liquid crystal compound having polymerizable functional groups. Among these, polymerizable liquid crystal compounds tend to readily produce cured products exhibiting high orientation properties; therefore, low-molecular-weight liquid crystal compounds are preferred.
[0278] The liquid crystal phase shown in the polymerizable liquid crystal compound can be suitable for nematic liquid crystals, smectic liquid crystals, cholesteric liquid crystals, disk-shaped liquid crystals, etc., but from the viewpoint of ease of manufacture and obtaining a highly ordered orientation state, nematic liquid crystals and smectic liquid crystals are preferred.
[0279] For ease of fixing the orientation structure, the polymerizable functional group is preferably a photopolymerizable group. Specifically, examples include acryloyl, methacryloyl, acryloyloxy, methacryloyloxy, acryloylamino, methacryloylamino, vinyl, vinyloxy, ethynyl, ethynyloxy, 1,3-butadienyl, 1,3-butadienyloxy, ethylene oxide, oxetane, glycidyl, glycidyloxy, styryl, styryloxy, etc. Among these, (meth)acryloyl is preferred.
[0280] As a polymerizable liquid crystal compound, liquid crystal compounds having polymerizable groups can be used in particular without limitation on molecular structure. For example, as a polymerizable liquid crystal compound contained in an optically anisotropic composition, a compound represented by the following formula (1) can be cited (hereinafter, sometimes referred to as "polymerizable liquid crystal compound (1)").
[0281] Q 1 -R 1 -A 11 -Y 1 -A 12 -(Y 2 -A 13 ) k -R 2 -Q 2 ···(1)
[0282] (In formula (1),)
[0283] -Q 1 Represents a hydrogen atom or a polymeric group;
[0284] -Q 2 Indicates a polymerizable group;
[0285] -R 1 -and R 2 -Each represents a chain-like organic group independently;
[0286] -A 11 -and A 13 - Each independently represents a portion of the structure, divalent organic group, or single bond shown in formula (2) below;
[0287] -A 12 - represents a portion of the structure or a divalent organic group as shown in formula (2) below;
[0288] -Y 1 -and Y 2 - Each of these can independently represent a single bond, -C(=O)O-, -OC(=O)-, -C(=S)O-, -OC(=S)-, -C(=O)S-, -SC(=O-, -CH2CH2-, -CH=CH-, -C≡C-, -C(=O)NH-, -NHC(=O-, -CH2O-, -OCH2-, -CH2S-, or SCH2-;
[0289] -A 11 -and A 13 One of them is a partial structure or a divalent organic group as shown in formula (2) below;
[0290] k is 1 or 2.
[0291] When k is 2, there are 2 -Y 2 -A 13 - They can be the same or different.
[0292] -Cy-X 2 -C≡CX 1 -···(2)
[0293] (In formula (2),)
[0294] -Cy- indicates a hydrocarbon cyclic group or a heterocyclic group;
[0295] -X 1 - indicates -C(=O)O-, -OC(=O)-, -C(=S)O-, -OC(=S-, -C(=O)S-, -SC(=O-, -CH2CH2-, -CH=CH-, -C(=O)NH-, -NHC(=O-, -CH2O-, -OCH2-, -CH2S-, or -SCH2-;
[0296] -X 2 - indicates a single bond, -C(=O)O-, -OC(=O)-, -C(=S)O-, -OC(=S)-, -C(=O)S-, -SC(=O)-, -CH2CH2-, -CH=CH-, -C(=O)NH-, -NHC(=O)-, -CH2O-, -OCH2-, -CH2S-, or -SCH2-.
[0297] It should be noted that -A 11 - In the case of the partial structure shown in equation (2), equation (1) can be either equation (1A) or equation (1B) as shown below.
[0298] Q 1 -R 1 -Cy-X 2 -C≡CX 1 -Y 1 -A 12 -(Y 2 -A 13 ) k -R 2 -Q 2 ···(1A)
[0299] Q 1 -R 1 -X 1 -C≡CX 2 -Cy-Y 1 -A 12 -(Y 2 -A 13 ) k -R 2 -Q 2 ···(1B)
[0300] Additionally -A 12 - In the case of the partial structure shown in equation (2), equation (1) can be either equation (1C) or equation (1D).
[0301] Q 1 -R 1 -A 11 -Y 1 -Cy-X 2 -C≡CX 1 -(Y 2 -A 13 ) k -R 2 -Q 2 ···(1C)
[0302] Q 1 -R 1 -A 11 -Y 1 -X 1 -C≡CX 2 -Cy-(Y 2 -A 13 ) k -R 2 -Q 2 ···(1D)
[0303] Additionally -A 13 - In the case of the partial structure shown in equation (2), equation (1) can be either equation (1E) or equation (1F).
[0304] Q 1 -R 1 -A 11 -Y 1 -A 12 -(Y 2 -Cy-X 2 -C≡CX 1 ) k -R 2 -Q 2 ···(1E)
[0305] Q 1 -R 1 -A 11 -Y 1 -A 12 -(Y 2 -X 1 -C≡CX 2 -Cy) k -R 2 -Q 2 ···(1F)
[0306] Similarly -A 11 -、-A 12 -、and-A 13When two or more of the components in equation (2) are partial structures, the orientation of the partial structures shown in equation (2) can be reversed independently.
[0307] In addition, as mentioned above, A 11 -、-A 12 -、and-A 13 -Each is an independent partial structure or divalent organic group as shown in formula (2), in addition, -A 11 -and A 13 - can be a single key, but -A 11 -and-A 13 - Not all are single keys.
[0308] As a polymerizable liquid crystal compound (1), the compound represented by the aforementioned formulas (1A), (1B), (1E) or (1F) is preferred for the purpose of obtaining high orientation.
[0309] When photopolymerizing a polymerizable liquid crystal compound, it is preferable to include a photopolymerization initiator in the optically anisotropic composition. The photopolymerization initiator can be a known substance.
[0310] From the viewpoint of ensuring optical function, the thickness of the cured film of the optical anisotropic composition is preferably 100 nm or more, more preferably 300 nm or more, and even more preferably 1 μm or more.
[0311] On the other hand, regarding the upper limit of thickness, from the viewpoint of facilitating the thinning of image display devices, it is preferably 50 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less.
[0312] A covering layer, an antistatic layer, a hard coating layer, an anchoring layer, a release layer, an easy-to-adhere layer, a protective layer, an anti-seepage color layer, a planarization layer, and other layers as needed can be formed on the cured film of the aforementioned optical anisotropic composition.
[0313] <<Adhesive sheet for this polarizing element>>
[0314] As an example of an embodiment of the present invention, the adhesive sheet with polarizing element (referred to as "the adhesive sheet with polarizing element") is configured to have the adhesive sheet I on at least one side of the coated polarizing element; in other words, it is configured to have the coated polarizing element on at least one side of the adhesive sheet I.
[0315] The adhesive sheet with polarizing element can be obtained, for example, by the following methods: forming the polarizing element on a substrate with release properties and then transferring the polarizing element to the surface of the adhesive sheet I; directly molding the adhesive sheet I onto a coated polarizing element; forming the coated polarizing element after molding the adhesive sheet I; etc.
[0316] Furthermore, the adhesive sheet with the polarizing element can be a structure formed by directly laminating the coated polarizing element and the adhesive sheet I, or it can be a case where other components are sandwiched between the two. The effects of the present invention can be enjoyed in either case.
[0317] At this time, as the "other components", examples that can be cited as the aforementioned "other image display device constituent components" include reflective sheets, light guide plates and light sources, diffusion films, prism sheets, liquid crystal panels, organic EL panels, anti-reflective films, color filters, polarizing plates, phase difference plates, glass substrates, glass covers, plastic covers, or composites of two or more of these components.
[0318] The coated polarizing element with adhesive sheet is the same as the coated polarizing element with adhesive layer.
[0319] <<Components of this image display device with adhesive layer>>
[0320] As an example of an embodiment of the present invention, an image display device component with an adhesive layer (referred to as "this image display device component with an adhesive layer") is an image display device component with an adhesive layer having an adhesive layer II (referred to as "this adhesive layer II") formed of the adhesive composition II or having the adhesive sheet II on at least one side of the image display device component.
[0321] The image display device component with adhesive layer can be, for example, an adhesive sheet with an image display device component having an image display device component on at least one side of the adhesive sheet II.
[0322] Alternatively, the image display device component with adhesive layer may also be an image display device component with adhesive layer having an image display device component on at least one side of adhesive layer II.
[0323] At this time, the aforementioned adhesive layer II can be directly applied to the components of the image display device, or the adhesive layer formed by the adhesive composition II can be formed on other substrates and then transferred to the components of the image display device.
[0324] Furthermore, the image display device component with adhesive layer can be a structure formed by directly laminating the image display device component with adhesive layer II or adhesive sheet II, or it can be a case where other components are sandwiched between the two. The effects of the present invention can be enjoyed in either case.
[0325] At this point, examples of "other components" include reflective sheets, light guide plates and light sources, diffusion films, prism sheets, liquid crystal panels, phase difference plates, glass substrates, polarizing plates, organic EL panels, electrodes, anti-reflective films, color filters, touch sensors, glass covers, plastic covers, or combinations of two or more of these components.
[0326] In addition to the above-mentioned components, antistatic layers, hard coatings, anchoring layers, release layers, easy-to-adhere layers, protective layers, anti-seepage color layers, and leveling layers, as well as other layers as needed, may also be sandwiched in.
[0327] <Components of an image display device using coated polarization elements>
[0328] As an example of a component of an image display device, an optical component that uses a coated polarizing element can be cited.
[0329] For this coated polarizing element, the foregoing description of the coated polarizing element with adhesive layer is referenced. In this case, the description of the polymeric liquid crystal compound in that description is also referenced.
[0330] <<Adhesive sheet for the components of this image display device>>
[0331] As an example of an embodiment of the present invention, the adhesive sheet for the image display device component (referred to as "the adhesive sheet for the image display device component") is configured to have the adhesive sheet II on at least one side of the image display device component.
[0332] The adhesive sheet for the image display device component can be obtained, for example, by the following methods: after forming the image display device component on a substrate with release properties, transferring the image display device component to the surface of the adhesive sheet II; directly molding the adhesive sheet onto the image display device component; forming the image display device component on the adhesive sheet II; etc.
[0333] Furthermore, the adhesive sheet for the components of the image display device can be a structure formed by directly stacking the image display device components and the adhesive sheet, or it can be a case where other components are sandwiched between the two. The effects of the present invention can be enjoyed in either case.
[0334] At this point, examples of "other components" include reflective sheets, light guide plates and light sources, diffusion films, prism sheets, liquid crystal panels, phase difference plates, glass substrates, polarizing plates, organic EL panels, electrodes, anti-reflective films, color filters, touch sensors, glass covers, plastic covers, or combinations of two or more of these components.
[0335] The image display device component with adhesive sheet is the same as the image display device component with adhesive layer.
[0336] <<This image display device>>
[0337] An example of an image display device (referred to as "this image display device") according to an embodiment of the present invention is an image display device having the adhesive layer I or II.
[0338] The form of adhesive layer I or II is not limited; it can be a pre-formed sheet adhesive product, i.e., adhesive sheet I or II.
[0339] As an example of this image display device, an image display device having a structure comprising an adhesive layer I or II formed of the adhesive composition I or II, the aforementioned coated polarizing element or the aforementioned image display device constituent component, and other components as needed, such as other image display device constituent components, stacked together.
[0340] In this image display device, such as Figure 2 or Figure 4 As shown, the structure can be formed by directly laminating a coated polarizing element or the aforementioned image display device component with the adhesive layer I or II. Alternatively, it can be as follows: Figure 3 As shown, other components, such as other image display devices, are sandwiched between the two. The effects of the present invention can be enjoyed in any of these cases.
[0341] At this time, "other components of the image display device" may include, for example, a reflective sheet, a light guide plate and a light source, a diffusion film, a prism sheet, a laminate, a liquid crystal panel, a phase difference plate, a glass substrate, a polarizing plate, an organic EL panel, electrodes, an anti-reflective film, a color filter, a touch sensor, a glass cover, a plastic cover, or two or more of these components integrated together.
[0342] In addition to the components mentioned above, antistatic layers, hard coatings, anchoring layers, release layers, easy-to-adhere layers, protective layers, anti-seepage color layers, and planarization layers, as well as other layers as needed, may also be sandwiched in.
[0343] In this image display device, adhesive layers I and II are preferably disposed closer to the viewable side than the coated polarizing element or the aforementioned image display device constituent components that are the adhered objects. Specifically, adhesive layer I or II is preferably used for bonding a glass cover or a plastic cover. This suppresses the deterioration of the polarizing element or image display device constituent components caused by incident light from the outside.
[0344] Organic EL display devices equipped with this adhesive layer II (see reference) Figure 5 In the case where the organic EL panel is configured to integrate a color filter, a black matrix, and an anti-reflective layer as needed (color filter-integrated organic EL panel), the adhesive layer II or the adhesive sheet II is preferably positioned closer to the visible side than the organic EL panel.
[0345] The color filter-integrated organic EL panel reduces external light reflection by incorporating a color filter, black matrix, and anti-reflection layer within the panel. Therefore, it eliminates the need for polarizing plates and retardation plates (circular polarizing plates) used in existing organic EL panels, which is beneficial for further thinning and weight reduction of image display devices.
[0346] Furthermore, the color filter-integrated organic EL panel absorbs the emitted light from the organic EL element without causing light loss, thus significantly improving the luminous efficiency of the organic EL element and consequently its luminous lifespan, which is beneficial for further high-performance image display devices.
[0347] By placing this adhesive layer II or this adhesive sheet II closer to the visible side than the organic EL panel, the degradation of the organic EL panel caused by incident light from the outside can be suppressed.
[0348] Specific examples of this image display device include liquid crystal displays, organic EL displays, inorganic EL displays, electronic paper, plasma displays, and microelectromechanical systems (MEMS) displays.
[0349] It should be noted that the above-mentioned laminated sheet can also be used on the surface of the glass cover or plastic cover of this image display device.
[0350] In addition, this adhesive layer I or II has the same transmittance, b* value, gelation rate and thickness characteristics as this adhesive sheet I or II, and can enjoy the preferred range of the characteristics shown in this adhesive sheet I or II.
[0351] <Explanation of Terminology>
[0352] In this invention, when the expression is "X~Y" (X and Y are arbitrary numbers), unless otherwise specified, it includes the meaning of "X or more and Y or less", and also includes the meaning of "preferably greater than X" or "preferably less than Y".
[0353] Additionally, when expressed as "X or above" (where X is any number) or "Y or below" (where Y is any number), it also includes the meaning of "preferably greater than X" or "preferably lower than Y".
[0354] In addition, the concept of "sheet" in this invention includes sheets, films, and strips.
[0355] Example
[0356] The present invention will now be described in further detail with reference to embodiments and comparative examples. However, the present invention is not limited to these embodiments.
[0357] <<Instructions for Raw Materials>>
[0358] The following examples and comparative examples illustrate the raw materials used in the preparation of the adhesive compositions.
[0359] [(Meth)acrylic polymer (A)]
[0360] • (Meth)acrylic polymer (A-1): is an acrylate copolymer polymer comprising 67% by mass of 2-ethylhexyl acrylate, 5% by mass of methyl acrylate, 10% by mass of ethyl acrylate, 14% by mass of 2-hydroxyethyl acrylate, and 4% by mass of 4-hydroxybutyl acrylate, wherein the mass-average molecular weight (Mw) of the aforementioned acrylate copolymer polymer, as determined by GPC, is 700,000.
[0361] • (Meth)acrylic polymer (A-2): An acrylate copolymer polymer in which 0.06 parts by mass of 2-methacryloyloxyethyl isocyanate is reacted in ethyl acetate solution to introduce polymeric carbon double bond groups into the side chain, relative to 100 parts by mass of a copolymer of 85% by mass of butyl acrylate and 15% by mass of 2-hydroxyethyl acrylate. The mass-average molecular weight (Mw) of the aforementioned acrylate copolymer polymer, as determined by GPC, is 900,000.
[0362] [UV absorber (B)]
[0363] • Ultraviolet absorber (B-1): 2,2'-Dihydroxy-4-methoxybenzophenone (manufactured by CHEMIPRO KASEIKAISHA,LTD., KEMISORB111)
[0364] • Ultraviolet absorber (B-2): 2,2',4,4'-Tetrahydroxybenzophenone (manufactured by SHIPRO KASEI KAISHA,LTD., SEESORB106)
[0365] • UV absorber (B-3): 2-(5-chloro-2H-benzotriazol-2-yl)-4-methyl-6-tert-butylphenol (manufactured by BASF, Tinuvin 326)
[0366] • Hydroxyl-containing benzophenone compounds (B1-1): 2,2'-Dihydroxy-4-methoxybenzophenone (manufactured by CHEMIPRO KASEI KAISHA,LTD., KEMISORB111)
[0367] • Hydroxyl-containing benzophenone compounds (B1-2): 2,2',4,4'-Tetrahydroxybenzophenone (manufactured by SHIPROKASEI KAISHA,LTD., SEESORB106)
[0368] [Free radical polymerization initiator (C)]
[0369] • Photolytic free radical polymerization initiator (C-1): 2,4,6-trimethylbenzoyl diphenylphosphine oxide (manufactured by IGMresins, Omnirad TPO H)
[0370] [Polyfunctional (meth)acrylates (D)]
[0371] • Multifunctional (meth)acrylate (D-1): Polypropylene glycol #700 diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., APG-700, molecular weight: 823)
[0372] • Multifunctional (meth)acrylate (D-2): Difunctional carbamate acrylate (manufactured by Mitsubishi Chemical Corporation, UV-3700B, molecular weight: 38000)
[0373] [other]
[0374] Solvent: Ethyl acetate
[0375] • Silane coupling agent: 3-epoxypropoxypropylmethyldiethoxysilane (Shin-Etsu Silicones, KBM403)
[0376] Rust inhibitor: 1,2,3-triazole
[0377] <Fabrication of Coated Polarizing Elements (Components of Image Displays)>
[0378] The coated polarizing element, which is used as a component of the image display in the evaluation, and the polymeric liquid crystal compound and pigment contained in the coated polarizing element are described.
[0379] (Synthesis of polymeric liquid crystal compounds)
[0380] [Liquid crystal compound (I-1)]
[0381] According to the description in Japanese Patent Application Publication No. 2020-042305, a liquid crystal compound (I-1) as shown in the following formula (I-1) was synthesized.
[0382]
[0383] (Pigment synthesis)
[0384] [Pigment (II-1)]
[0385] The pigment (II-1) shown in the following formula (II-1) was synthesized according to the synthesis method described below.
[0386]
[0387] Synthesis of (II-1-a):
[0388] In an ice-cooled reactor, tetrahydrofuran (100 mL), sodium hydride (60% purity, 6.7 g, 168.0 mmol), and a mixture of diethyl (4-nitrobenzyl)phosphonate (18.0 g, 65.9 mmol), 4-butylbenzaldehyde (9.1 g, 56.1 mmol), and tetrahydrofuran (50 mL) were added dropwise over 10 minutes. After washing with tetrahydrofuran (30 mL), the mixture was stirred at 50 °C for 0.5 hours. The reaction mixture was injected into water, extracted with ethyl acetate, washed with water and saturated brine, and the solvent was removed by distillation. The resulting crude substance was dissolved in ethyl acetate (20 mL) by heating, hexane (50 mL) was added, and the mixture was cooled. The precipitate was filtered off, washed with hexane, and dried under reduced pressure to give 15.0 g of (II-1-a).
[0389] Synthesis of (II-1-b):
[0390] Mix (II-1-a) (15.0 g, 53.3 mmol), tetrahydrofuran (150 mL), and iron powder (13.9 g, 248.9 mmol). Add ammonium chloride (13.3 g, 248.6 mmol) dissolved in water (30 mL) dropwise and stir at 50 °C for 3 hours. Filter with diatomaceous earth, extract with ethyl acetate, wash with water and saturated brine, and remove the solvent by distillation. Suspend the resulting crude product in hexane, filter off the precipitate, wash with hexane, and dry to obtain 10.9 g of (II-1-b).
[0391] Synthesis of (II-1):
[0392] Mix (II-1-b) (2.51 g, 10.0 mmol), N-methylpyrrolidone (40 mL), concentrated hydrochloric acid (2.2 mL), and water (20 mL), cool to 3 °C, add sodium nitrite (789 mg, 11.4 mmol), and stir at 15 °C for 3.5 hours.
[0393] Mix 1-phenylpyrrolidine (1.47 g, 10.0 mmol), methanol (60 mL), and water (30 mL), and adjust the pH to 3.5 with concentrated hydrochloric acid. Add an aqueous sodium hydroxide solution, and while maintaining the pH at 3–5, add the liquid containing the above diazonium salt dropwise, and stir at 15°C for 3 hours.
[0394] The precipitate was filtered, washed with water, and dried under reduced pressure. The crude product was purified by silica gel column chromatography (hexane / dichloromethane) to give 3.06 g of pigment (II-1) as a red solid.
[0395] [Pigment (II-2)]
[0396] The pigment (II-2) shown in the following formula (II-2) was synthesized according to the synthesis method described below.
[0397]
[0398] Synthesis of (II-2):
[0399] (II-1-b) (1.0 g, 4.0 mmol) and N-methylpyrrolidone (13 mL) were mixed, and concentrated hydrochloric acid (1.0 g, 10.0 mmol) was added. After cooling in an ice bath, sodium nitrite (0.3 g, 4.4 mmol) dissolved in water (1.3 mL) was added, and the mixture was stirred for 1 hour. The reaction solution was coupled with 1-phenylpiperidine (0.6 g, 4.0 nmol) dissolved in methanol (25 mL) and water (6.5 mL) at pH 7. The precipitate was filtered off, washed with water, and dried under reduced pressure. The crude product was purified by silica gel column chromatography (hexane / dichloromethane) to give 760 mg of pigment (II-2) as an orange solid.
[0400] The chemical structures of the liquid crystal compound and pigment synthesized above are shown below. It should be noted that, in the formula, C... 11 H 22 This refers to the presence of 11 methylene chains bonded together in a straight-chain configuration.
[0401]
[0402] The chemical structures of pigments (II-3) and (II-4) used in the examples and comparative examples are shown below.
[0403]
[0404] (Preparation of optically anisotropic compositions)
[0405] To 69.31 parts of cyclopentanone, 28.57 parts of liquid crystal compound (I-1), 0.10 parts of pigment (II-1), 0.43 parts of pigment (II-2), 0.39 parts of pigment (II-3) (manufactured by Hayashibara Co., Ltd.), 0.90 parts of pigment (II-4) (manufactured by Showa Chemical Co., Ltd.), 0.23 parts of the following initiator (PI-1), and 0.34 parts of BYK-361N (manufactured by BYK-Chemie Co., Ltd.) were added. After heating and stirring at 80°C, the mixture was filtered using a syringe equipped with a syringe filter (manufactured by Membrane Solutions Co., Ltd., PTFE13045, 0.45 μm diameter) to obtain an optically anisotropic composition.
[0406]
[0407] (Manufacturing of coated polarization elements)
[0408] On a substrate with a polyimide alignment film (LX1400, manufactured by Hitachi Chemical DuPont MicroSystems, Ltd., formed by brushing) formed on glass, the optically anisotropic composition prepared above was spin-coated. After drying at 120°C for 2 minutes, it was cooled to the liquid crystal phase and exposed to an exposure of 500 mJ / cm². 2 Polymerization was performed using a 365nm reference to obtain a coated polarization element with a thickness of approximately 3μm.
[0409] Furthermore, a covering layer is further formed on the coated polarizing element using a covering composition, as described below.
[0410] The curable (meth)acryloyl copolymer (R-1) contained in the covering composition is synthesized by the following method.
[0411] In a flask equipped with a thermometer, stirrer, and reflux condenser, propylene glycol monomethyl ether (157 parts by mass), glycidyl methacrylate (98 parts by mass), methacrylate (1.0 part by mass), ethyl acrylate (1.0 part by mass), 2,2'-azobis(2,4-dimethylpentanilonitrile) (1.0 part by mass), and γ-trimethoxysilylpropanethiol (KBM-803 manufactured by Shin-Etsu Chemical Co., Ltd.) 1.9 parts by mass were added, and the mixture was reacted at 65°C for 3 hours.
[0412] Then, 0.5 parts by mass of 2,2'-azobis(2,4-dimethylpentanonitrile) were added, and after reacting for 3 hours, 138 parts by mass of propylene glycol monomethyl ether and 0.45 parts by mass of p-methoxyphenol were added, and the mixture was heated to 100°C.
[0413] Next, acrylic acid (51 parts by mass) and triphenylphosphine (3.1 parts by mass) were added, and the mixture was reacted at 110°C for 6 hours to obtain a (meth)acryloyl copolymer (R-1) with a carbon-carbon double bond content (acryloyl equivalent (acryloyl group introduction amount)) of 4.6 mmol / g. The mass-average molecular weight (Mw) was 17700.
[0414] A coating composition was obtained by mixing and stirring 23.08 parts of a 65% solution of propylene glycol monomethyl ether of a curable (meth)acryloyl copolymer (R-1), 0.13 parts of the following photopolymerization initiator (PI-2), 0.40 parts of BYK-3550 (manufactured by BYK-Chemie), and 76.39 parts of ethanol.
[0415] The coating composition was spin-coated onto the aforementioned coated polarizing element, dried at 50°C for 2 minutes, and then exposed to an exposure of 500 mJ / cm. 2 (Based on 365nm) polymerization is performed, followed by heating at 80°C for 5 minutes to stack a capping layer with a thickness of about 5μm, resulting in a coated polarizing element with a capping layer.
[0416] By covering a commercially available polarizing plate with the obtained coated polarizing element with a protective layer and rotating it, the resulting brightness and darkness can be confirmed, demonstrating its good performance as a polarizing film.
[0417]
[0418] [Example I-1]
[0419] 200 parts by mass of a solution of (meth)acrylic acid polymer (A-1) (diluent: ethyl acetate, solid content concentration: 50% by mass), 6 parts by mass of ultraviolet absorber (B-1), 3 parts by mass of photopyrolysis free radical polymerization initiator (C-1), 25 parts by mass of polyfunctional (meth)acrylic acid ester (D-1), 0.3 parts by mass of 3-epoxypropoxypropylmethyldiethoxysilane (Shin-Etsu Silicone, KBM403) as a silane coupling agent, 0.3 parts by mass of 1,2,3-triazole as a rust inhibitor, and 101 parts by mass of ethyl acetate were uniformly mixed to prepare adhesive composition I-1.
[0420] On a 100 μm thick release film (DIAFOIL MRV manufactured by Mitsubishi Chemical Corporation) that has undergone silicone release treatment, the adhesive composition I-1 is spread into a sheet such that the thickness of the adhesive composition I-1 after solvent drying is 50 μm.
[0421] Next, the sheet-like adhesive composition I-1, together with the release film, is placed in a dryer heated to 95°C and kept for 10 minutes to allow the solvent contained in the adhesive composition I-1 to evaporate.
[0422] Then, a 75 μm thick release film (DIAFOIL MRQ manufactured by Mitsubishi Chemical Corporation) that has undergone silicone release treatment is laminated onto the sheet-like adhesive composition I-1 after the solvent has been dried, to form a laminate. The adhesive composition I-1 is then irradiated with a high-pressure mercury lamp through the release film at a cumulative dose of 1000 mJ / cm² at a wavelength of 365 nm. 2 The cumulative irradiation dose at a wavelength of 405 nm is 1400 mJ / cm². 2 The adhesive sheet I-1 (adhesive sheet thickness: 50μm) was obtained by irradiating it with light in a certain way, with release films stacked on both sides of the surface and back.
[0423] [Examples I-2 to I-4, Comparative Examples I-1 to I-2]
[0424] The types and amounts of (meth)acrylic polymers (A), ultraviolet absorbers (B), free radical polymerization initiators (C), polyfunctional (meth)acrylates (D), and other additives used are as shown in Table 1. Except for this, adhesive compositions I-2 to I-6 and adhesive sheets I-2 to I-6 with release films are prepared in the same manner as in Example I-1.
[0425] <Evaluation>
[0426] The adhesive compositions I-1 to I-6 and adhesive sheets I-1 to I-6 obtained in the Examples and Comparative Examples are measured / evaluated as follows.
[0427] [Light transmittance]
[0428] The release films on both sides of the adhesive sheet with release film prepared in the examples and comparative examples were peeled off in sequence. The adhesive sheet (thickness 50 μm) was attached by clamping two sheets of soda-lime glass (thickness 0.5 mm). It was then subjected to autoclave treatment (60°C, gauge pressure 0.2 MPa, 20 minutes) for fine finishing and attachment to prepare a sample for optical property evaluation.
[0429] The transmittance of the prepared optical property evaluation sample in the wavelength range of 360–430 nm was measured using a spectrophotometer (manufactured by Shimadzu Corporation; equipment name "UV2450").
[0430] [b* value]
[0431] According to JIS Z8781-4, the b* value of the prepared optical property evaluation sample was determined using a spectrophotometer (manufactured by Suga Test Instruments Co., Ltd., equipment name "SC-P").
[0432] [Gel ratio]
[0433] The gelation rate of the adhesive compositions prepared intermediately in the examples and comparative examples was determined according to the following steps.
[0434] 1) Weigh the adhesive composition (W1) and encapsulate it in a pre-measured weight of SUS mesh (W0).
[0435] 2) Immerse the above SUS mesh in 100 mL of ethyl acetate for 24 hours.
[0436] 3) Remove the SUS mesh and dry it at 75°C for 4.5 hours.
[0437] 4) Calculate the mass (W2) after drying, and determine the gelation rate of the adhesive composition according to the following formula.
[0438] gelation rate (%) = 100 × (W2 - W0) / W1
[0439] [Adhesive strength]
[0440] For the adhesive sheets with release films prepared in the examples and comparative examples, one release film was peeled off, and a polyethylene terephthalate film (manufactured by Toyobo Co., Ltd.; trade name "Cosmoshine A4300", thickness 100 μm) serving as the lining film was rolled together using a hand roller. It was then cut into strips 10 mm wide × 100 mm long, and the adhesive surface exposed by peeling off the remaining release film was rolled onto soda-lime glass using a hand roller. Autoclaving was performed (60°C, gauge pressure 0.2 MPa, 20 minutes) for fine finishing and bonding, and samples for adhesive strength testing were prepared.
[0441] Using a universal testing machine (INSTRON Corporation, equipment name "5965"), the lining film was stretched at a 180° angle and a peeling speed of 60 mm / min while the adhesive sheet was peeled off from the glass. The tensile strength was measured using a load sensor, and the 180° peel strength (N / cm) of the adhesive sheet to the glass was measured and shown in Table 1 as "adhesive force".
[0442] [Protective Function of Coated Polarizing Elements]
[0443] For the adhesive sheet with a release film prepared in the examples and comparative examples, one release film is peeled off, and the adhesive sheet is pressed onto the cover layer of the coated polarizing element by a hand roller. The adhesive surface exposed by peeling off the remaining release film is then rolled onto the soda-lime glass by a hand roller. Autoclave treatment (60°C, gauge pressure 0.2 MPa, 20 minutes) is performed for fine-tuning and attachment, and a sample for testing the protective function of the coated polarizing element is prepared.
[0444] For the aforementioned samples, a xenon lightfastness tester (manufactured by Atlas Co., Ltd., equipment name "Ci4000") was used at an illuminance of 0.55 W / cm². 2 A 40-hour lightfastness test was conducted under ultraviolet (340nm) irradiation conditions.
[0445] As a result of the lightfastness test, the change in polarization at a wavelength of 595 nm before and after the lightfastness test (polarization before the test - polarization after the test) is shown in Table 1.
[0446] The polarization (Pe) is calculated as follows: The linearly polarized measurement light is incident on the anisotropic pigment film, and the "transmittance of the anisotropic pigment film to polarized light in the absorption axis direction" and the "transmittance of the anisotropic pigment film to polarized light in the polarization axis direction" are measured using a spectrophotometer equipped with a Glan-Thompson polarizer (manufactured by Otsuka Electronics Co., Ltd., product name "RETS-100"). The result is calculated according to the following formula.
[0447] Pe = (Ty - Tz) / (Ty + Tz)
[0448] (in the formula,
[0449] Tz is the transmittance of the anisotropic pigment film for polarized light along the absorption axis.
[0450] Ty represents the transmittance of the anisotropic pigment film for polarized light along the polarization axis.
[0451] The following criteria will be used for evaluation.
[0452] ○(good): The change in polarization before and after the lightfastness test is less than 0.25.
[0453] ×(poor): Values where the change in polarization before and after the lightfastness test is greater than 0.25.
[0454] The results obtained from the measurement and evaluation are shown in Table 1.
[0455] [Table 1]
[0456]
[0457] As can be seen from the above embodiments and the test results conducted by the inventors to date, in order to prevent the polarization performance of coated polarizing elements from degrading over time due to exposure, the transmittance at a wavelength of 400 nm is required to be at least lower than that in Comparative Example 1.
[0458] As can be seen from the above embodiments and the test results conducted by the inventors to date, for an adhesive composition containing (meth)acrylic polymer (A) and ultraviolet absorber (B), if the transmittance of the adhesive layer formed by the aforementioned adhesive composition at a wavelength of 400 nm is set to 50% or less, then by using it in combination with a coated polarizing element, the polarization performance of the coated polarizing element can be prevented from decreasing over time due to exposure.
[0459] [Example II-1]
[0460] 200 parts by mass of a solution of (meth)acrylic acid polymer (A-1) (diluent: ethyl acetate, solid content concentration: 50% by mass), 6 parts by mass of a hydroxyl-containing benzophenone compound (B1-1), 3 parts by mass of a photolytic free radical polymerization initiator (C-1), 25 parts by mass of a multifunctional (meth)acrylic acid ester initiator (D-1), 0.3 parts by mass of 3-epoxypropoxypropylmethyldiethoxysilane (Shin-Etsu Silicone, KBM403) as a silane coupling agent, 0.3 parts by mass of 1,2,3-triazole as a rust inhibitor, and 101 parts by mass of ethyl acetate were uniformly mixed to prepare adhesive composition II-1.
[0461] On a 100 μm thick release film (DIAFOIL MRV manufactured by Mitsubishi Chemical Corporation) that has undergone silicone release treatment, the adhesive composition II-1 after solvent drying is spread into a sheet such that the thickness is 50 μm.
[0462] Next, the sheet-like adhesive composition II-1, together with the release film, is placed in a dryer heated to 95°C and kept for 10 minutes to allow the solvent contained in the adhesive composition II-1 to evaporate.
[0463] Subsequently, a 75 μm thick release film (DIAFOIL MRQ manufactured by Mitsubishi Chemical Corporation) that has undergone silicone release treatment is laminated onto the sheet-like adhesive composition II-1 after the solvent has been dried, forming a laminate. The adhesive composition II-1 is then irradiated with a high-pressure mercury lamp through the release film at a cumulative dose of 1000 mJ / cm² at a wavelength of 365 nm. 2 The cumulative irradiation dose at a wavelength of 405 nm is 1400 mJ / cm². 2 By irradiating with light in a certain way, an adhesive sheet II-1 with a release film (adhesive sheet thickness: 50μm) is obtained, which has a release film stacked on both sides of the surface and back.
[0464] [Examples II-2 to II-3, Reference Example II-1, Comparative Examples II-1 to II-2]
[0465] The types and amounts of (meth)acrylic polymers (A), ultraviolet absorbers (B), free radical polymerization initiators (C), polyfunctional (meth)acrylates (D), and other additives used are as shown in Table 2. Except for this, adhesive compositions II-2 to II-6 and adhesive sheets II-2 to II-6 with release films are prepared in the same manner as in Example II-1.
[0466] <Evaluation>
[0467] The adhesive compositions II-1 to II-6 and adhesive sheets II-1 to II-6 obtained in the Examples, Reference Examples and Comparative Examples are measured / evaluated as follows.
[0468] [Light transmittance]
[0469] The release films on both sides of the adhesive sheet with release film prepared in the examples, reference examples and comparative examples were peeled off in sequence. The adhesive sheet (thickness 50 μm) was attached by clamping two sheets of soda-lime glass (thickness 0.5 mm). It was subjected to autoclave treatment (60°C, gauge pressure 0.2 MPa, 20 minutes) for fine processing and attachment to prepare a sample for optical property evaluation.
[0470] The transmittance of the prepared optical property evaluation sample in the wavelength range of 360–430 nm was measured using a spectrophotometer (manufactured by Shimadzu Corporation; equipment name "UV2450").
[0471] [b* value]
[0472] According to JIS Z8781-4, the b* value of the prepared optical property evaluation sample was determined using a spectrophotometer (manufactured by Suga Test Instruments Co., Ltd., equipment name "SC-P").
[0473] [Gel ratio]
[0474] The gelation rate of the adhesive compositions prepared intermediately in the Examples, Reference Examples and Comparative Examples was determined according to the following steps.
[0475] 1) Weigh the adhesive composition (W1) and encapsulate it in a pre-measured weight of SUS mesh (W0).
[0476] 2) Immerse the above SUS mesh in 100 mL of ethyl acetate for 24 hours.
[0477] 3) Remove the SUS mesh and dry it at 75°C for 4.5 hours.
[0478] 4) Calculate the mass (W2) after drying, and determine the gelation rate of the adhesive composition according to the following formula.
[0479] gelation rate (%) = 100 × (W2 - W0) / W1
[0480] [Adhesive strength]
[0481] For the adhesive sheets with release films prepared in the examples, reference examples, and comparative examples, one release film was peeled off, and a polyethylene terephthalate film (manufactured by Toyobo Co., Ltd.; trade name "Cosmoshine A4300", thickness 100 μm) serving as the lining film was rolled together using a hand roller. It was cut into strips 10 mm wide × 100 mm long, and the adhesive surface exposed by peeling off the remaining release film was rolled onto soda-lime glass using a hand roller. Autoclaving was performed (60°C, gauge pressure 0.2 MPa, 20 minutes) for fine finishing and bonding, and samples for adhesive strength testing were prepared.
[0482] Using a universal testing machine (INSTRON Corporation, equipment name "5965"), the lining film was stretched at a 180° angle and a peeling speed of 60 mm / min while the adhesive sheet was peeled off from the glass. The tensile strength was measured using a load sensor, and the 180° peel strength (N / cm) of the adhesive sheet to the glass was measured and shown in Table 2 as "Adhesive Force".
[0483] [Durability]
[0484] For the aforementioned optical evaluation samples, a xenon lightfastness testing machine (manufactured by Atlas Co., Ltd., equipment name "Santest XPS+") was used at an illuminance of 60 W / cm². 2 (300~400nm), black panel temperature: 63℃. Under ultraviolet irradiation conditions, a 100-hour test was conducted. The b* value of the tested sample was determined according to JIS Z8781-4 using a spectrophotometer (manufactured by Suga Test Instruments Co., Ltd., equipment name "SC-P").
[0485] The following criteria will be used for evaluation.
[0486] ○(good): The change in b* value before and after the durability test is less than 3.
[0487] ×(poor): The change in b* value before and after the durability test is greater than 3.
[0488] [Protective Functions of Components Constituting the Image Display Device]
[0489] For the adhesive sheets with release films prepared in the embodiments, reference examples, and comparative examples, one release film is peeled off, and the adhesive sheet is pressed onto the image display device component by a hand roller. The adhesive surface exposed by peeling off the remaining release film is then rolled onto the soda-lime glass by a hand roller. Autoclave treatment (60°C, gauge pressure 0.2 MPa, 20 minutes) is performed for fine-tuning and attachment, and a sample for measuring the protective function of the image display device component is prepared.
[0490] For the aforementioned samples, a xenon lightfastness tester (manufactured by Atlas Co., Ltd., equipment name "Ci4000") was used at an illuminance of 0.55 W / cm². 2 A 40-hour lightfastness test was conducted under ultraviolet (340nm) irradiation conditions.
[0491] As a result of the lightfastness test, the change in polarization at a wavelength of 595 nm before and after the lightfastness test (polarization before the test - polarization after the test) is shown in Table 2.
[0492] The polarization (Pe) is calculated as follows: The linearly polarized measurement light is incident on the anisotropic pigment film, and the "transmittance of the anisotropic pigment film to polarized light in the absorption axis direction" and the "transmittance of the anisotropic pigment film to polarized light in the polarization axis direction" are measured using a spectrophotometer equipped with a Glan-Thompson polarizer (manufactured by Otsuka Electronics Co., Ltd., product name "RETS-100"). The result is calculated according to the following formula.
[0493] Pe = (Ty - Tz) / (Ty + Tz)
[0494] (in the formula,
[0495] Tz is the transmittance of the anisotropic pigment film for polarized light along the absorption axis.
[0496] Ty represents the transmittance of the anisotropic pigment film for polarized light along the polarization axis.
[0497] The following criteria will be used for evaluation.
[0498] ○(good): The change in polarization before and after the lightfastness test is less than 0.25.
[0499] ×(poor): The change in polarization before and after the lightfastness test is greater than 0.25.
[0500] [Overall Evaluation]
[0501] The case where both the durability test and the evaluation of the protective function of the components of the image display device are rated as "○ (good)" is judged as "○ (good)". The case where either or both of the durability test and the evaluation of the protective function of the components of the image display device are rated as "× (poor)" is judged as "× (poor)".
[0502] The results obtained from the measurement and evaluation are shown in Table 2.
[0503] [Table 2]
[0504]
[0505] As can be seen from the above embodiments and the test results conducted by the inventors to date, in order to obtain excellent lightfastness reliability, the transmittance at a wavelength of 400 nm in Reference Example II-1 must be less than 30%.
[0506] Explanation of reference numerals in the attached figures
[0507] 1. The adhesive sheet for coating-type polarizing elements or adhesive sheet for components of image display devices according to the present invention
[0508] 2. Glass cover or plastic cover
[0509] 3. Coated polarizing element (polarizing layer) or optical anisotropic layer (polarizing layer)
[0510] 4-Orientation Film
[0511] 5. Coated polarization element (phase retardation layer) or optical anisotropic layer (phase retardation layer)
[0512] 6 polarizing plates
[0513] 7. Phase Difference Plate
[0514] 8 LCD panels
[0515] 9 Organic EL Panel
[0516] 10 resin sheets or glass
[0517] 11a, 11b release films
[0518] 12a~12c Adhesive layer or adhesive layer
Claims
1. An adhesive composition for coating-type polarizing elements, comprising a (meth)acrylic polymer (A), an ultraviolet absorber (B), and a free radical polymerization initiator (C), wherein the transmittance of the adhesive layer formed by said adhesive composition is less than 30% at a wavelength of 400 nm and more than 80% at a wavelength of 430 nm, and as specified in JIS Z8781-4. The color space represented The value is below 3.
0.
2. The adhesive composition for coating polarizing elements according to claim 1, further comprising polyfunctional (meth)acrylate (D).
3. The adhesive composition for coating-type polarizing elements according to claim 1 or 2, wherein, The content of the ultraviolet absorber (B) is 0.1 parts by mass or more relative to 100 parts by mass of the (meth)acrylic polymer (A).
4. The adhesive composition for coating-type polarizing elements according to claim 1 or 2, wherein, The ultraviolet absorber (B) contains a benzophenone structure.
5. The adhesive composition for coating-type polarizing elements according to claim 2, wherein, The multifunctional (meth)acrylate (D) is a (meth)acrylate oligomer with a molecular weight of 3000 or more.
6. The adhesive composition for coating-type polarizing elements according to claim 1 or 2, wherein, The (meth)acrylic polymer (A) has polymerizable carbon double bond groups in its side chain.
7. The adhesive composition for coating-type polarizing elements according to claim 1 or 2, wherein, The free radical polymerization initiator (C) is a photodegradation type free radical polymerization initiator.
8. The adhesive composition for coating polarizing elements according to claim 1 or 2, which can be cured in multiple stages.
9. An adhesive sheet for a coated polarizing element, comprising an adhesive layer formed using the adhesive composition for a coated polarizing element according to any one of claims 1 to 8.
10. The adhesive sheet for coating polarizing elements according to claim 9, wherein the gelation rate is 20% or more and 95% or less.
11. The adhesive sheet for coating polarizing elements according to claim 9, wherein the thickness is 10 μm or more and 175 μm or less.
12. An adhesive sheet with a release film, comprising a structure formed by laminating the adhesive sheet for a coating polarizing element according to any one of claims 9 to 11 with the release film.
13. A laminated sheet comprising, on at least one side of any one of claims 9 to 11, a resin sheet or thin-film glass having one or more resins selected from the group consisting of cyclic olefin resins, cellulose triacetate resins, polymethyl methacrylate resins, epoxy resins, polyester resins, and polyimide resins as the main component resin.
14. A coated polarizing element with an adhesive layer, wherein at least one side of the coated polarizing element has an adhesive layer formed from an adhesive composition for coated polarizing elements according to any one of claims 1 to 8.
15. An adhesive sheet with a polarizing element, wherein at least one side of the adhesive sheet for a coated polarizing element according to any one of claims 9 to 11 is provided with a coated polarizing element.
16. An image display device having a configuration in which a coated polarizing element and an adhesive layer are directly laminated or laminated using other components. The adhesive layer is formed from an adhesive composition comprising a (meth)acrylic polymer (A), an ultraviolet absorber (B), and a free radical polymerization initiator (C), and has a transmittance of less than 30% at a wavelength of 400 nm and a transmittance of more than 80% at a wavelength of 430 nm, as specified in JIS Z8781-4. The color space represented The value is below 3.
0.
17. The image display device according to claim 16, wherein, The transmittance of the adhesive layer at a wavelength of 380 nm is less than 20%.
18. The image display device according to claim 16 or 17, wherein, The transmittance T(380) of the adhesive layer at a wavelength of 380 nm, the transmittance T(430) at a wavelength of 430 nm, and The values satisfy the relationship between the following equations (I) and (II). 0 ≤ T(380)× ≤50 (I) 70≤ T(430)× ≤220 (II)。 19. An adhesive sheet for a component of an image display device, formed from an adhesive composition comprising a (meth)acrylic acid polymer (A), a hydroxyl-containing benzophenone compound (B1), and a free radical polymerization initiator (C), and having a transmittance of less than 30% at a wavelength of 400 nm, and conforming to the specifications in JIS Z8781-4. The color space represented The value is below 3.
0.
20. The adhesive sheet for the constituent components of the image display device according to claim 19, wherein the transmittance at a wavelength of 380 nm is less than 20%.
21. The adhesive sheet for the constituent components of the image display device according to claim 19 or 20, wherein the transmittance at a wavelength of 430 nm is 50% or more.
22. The adhesive sheet for a component of an image display device according to claim 19 or 20, wherein the transmittance T(380) at a wavelength of 380 nm, the transmittance T(430) at a wavelength of 430 nm, and The values satisfy the relationship between the following equations (I) and (II). 0 ≤ T(380)× ≤50 (I) 70≤ T(430)× ≤220 (II)。 23. The adhesive sheet for a component of an image display device according to claim 19 or 20, wherein, The content of the hydroxyl-containing benzophenone compound (B1) is 0.1 parts by mass or more relative to 100 parts by mass of the (meth)acrylic polymer (A).
24. The adhesive sheet for the constituent components of the image display device according to claim 19 or 20, further comprising polyfunctional (meth)acrylate (D).
25. The adhesive sheet for a component of an image display device according to claim 19 or 20, wherein, The (meth)acrylic polymer (A) has photoactive sites in its side chain.
26. The adhesive sheet for a component of an image display device according to claim 24, wherein, The multifunctional (meth)acrylate (D) is a (meth)acrylate oligomer with a molecular weight of 3000 or more.
27. The adhesive sheet for a component of an image display device according to claim 19 or 20, wherein, The free radical polymerization initiator (C) is a photopolymerization initiator with extremely high absorption at a wavelength of at least 400-430 nm.
28. The adhesive sheet for a component of an image display device according to claim 19 or 20, wherein, The mass ratio of the hydroxyl-containing benzophenone compound (B1) to the free radical polymerization initiator (C) is (B1):(C) = 1:0.05~1:
20.
29. The adhesive sheet for a component of an image display device according to claim 19 or 20, wherein the gelation rate is 20% or more and 95% or less.
30. The adhesive sheet for a component of an image display device according to claim 19 or 20, wherein the thickness is 10 μm or more and 175 μm or less.
31. The adhesive sheet for a component of an image display device according to claim 19 or 20, wherein, The image display device is composed of reflective sheet, light guide plate and light source, diffusion film, prism sheet, liquid crystal panel, phase difference plate, glass substrate, polarizing plate, organic EL panel, electrode, anti-reflective film, color filter, touch sensor, glass cover, plastic cover, or two or more of these components integrated together.
32. The adhesive sheet for the constituent components of the image display device according to claim 19 or 20, which can be cured in multiple stages.
33. The adhesive sheet for the constituent components of the image display device according to claim 19 or 20, wherein it is composed of two or more layers.
34. An adhesive sheet with a release film, comprising a structure formed by laminating the adhesive sheet and the release film for the image display device constituent components as described in any one of claims 19 to 33.
35. An adhesive sheet with an image display device component, wherein the image display device component has an adhesive sheet for the image display device component as described in any one of claims 19 to 33.
36. A laminated sheet, wherein at least one side of the adhesive sheet for the image display device constituent component according to any one of claims 19 to 33 comprises a resin sheet or thin film glass having one or more resins selected from the group consisting of cyclic olefin resins, cellulose triacetate resins, polymethyl methacrylate resins, epoxy resins, polyester resins and polyimide resins as the main component resin.
37. An image display device comprising an adhesive sheet for forming components of the image display device according to any one of claims 19 to 33.
Citation Information
Patent Citations
Ultraviolet-curable acrylic adhesive composition, ultraviolet-curable acrylic adhesive layer, polarization film with adhesive layer, method for producing ultraviolet-curable acrylic adhesive layer and image display device
JP2016155981A
Optical adhesive sheet
JP2019214722A
Anisotropic dye film-forming composition, anisotropic dye film, and optical element
JP2020042305A
Polarizing film with pressure-sensitive adhesive layer, and image display device
CN108369305A
Ultraviolet-curable acrylic adhesive composition, ultraviolet-curable acrylic adhesive layer, adhesive layer-equipped polarization film, method for producing ultraviolet-curable acrylic adhesive layer, and image display device
CN109348720A